Fates of potassium during co-pyrolysis of corn stalk and plastic film components - Chao Fan; Jing Liu; Junxia Wang; Jian Li; Zixi Han; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Biomass and Bioenergy, 2027)

Ozone-persulfate molecular energy-level matching regulates dissolved organic matter degradation and transformation in leachate aerobic effluent - Junda Lai; Jun Cui; Yechen An; Zhenbei Wang; Yunjie Liao; Fan Li; Chen Li; Yatao Liu; Fei Qi; Zhonglin Chen (Water Research, 2026)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

Unveiling microscale aerosol formation pathways in combustion systems: in situ evidence from cigarette burning cones - Jiaying Li; Huapeng Cui; Meijuan Fan; Li Chen; Yaqiong Qin; Ruihong Liu; Mantang Chen; Yu Liu; Jizhao Guo; Shaofeng Liu; Xiaobing Zhang; Fuwei Xie; et al. (Biomass and Bioenergy, 2026)

Natural drivers of annual total carbon uptake dynamics on the Tibetan Plateau since the Last Glacial Maximum - Anning Cui; Yajie Dong; Jianping Zhang; Baiqing Xu; Zhongzhe Gao; Wenchao Zhang; Baoshuo Fan; Deke Xu; Hao Li; Houyuan Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Targeted regulation and extraction mechanism of rare earth elements and thorium during the decomposition of rare earth concentrates - Xiaowei Zhang; Likai Zang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Jianguo Cui; Na Li; Xiaodong Wang; Ruifeng Ma (Minerals Engineering, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Cooling performance of a self-regulating mechanical ventilation system: A case study for Qinghai-Tibet expressway Tuotuohe pilot section - Jianbin Hao; Simao Fan; Jianbing Chen; Caihong Zhao; Jinping Li; Zhiyun Liu; Fuqing Cui (Cold Regions Science and Technology, 2026)

Vegetation and climate context of rice domestication since the late Pleistocene in the lower Yangtze River, China - Baoshuo Fan; Jianping Zhang; Yajie Dong; Deke Xu; Anning Cui; Xiujia Huan; Leping Jiang; Hao Li; Yuecong Li; Naiqin Wu; Houyuan Lu (Quaternary Science Reviews, 2026)

Discovery of garnet-bearing peraluminous ferroan granites in the Trans-North China Orogen: Evidence for anatexis of residual metasedimentary crust in a hot collisional orogen - Jing-Jing Fan; Caiyun Lan; Yong-Min Li; Jun Rao; Zi-Long Wang; Ze-Xian Cui; Meng-Jing Li; Xiaoping Long (Precambrian Research, 2026)

Spatial patterns of modern pollen deposition as a basis for paleoecological interpretation in deep lakes: Insights from Fuxian Lake, Southwest China - Fan Xu; Sidan Cui; Jinhao Dong; Yawen Ge; Wenlei Luo; Lixin Xu; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Electronic modulation in 3D tubular sulfur-doped carbon nitride via thiophene-skeleton bridging: Promoting n→π* transition for wastewater remediation coupled with H2 evolution - Xuan Guan; Jiachun Wu; Hui Fan; Huixia Li; Liang Zhang; Haijiao Xie; Yanjuan Cui (Journal of Environmental Chemical Engineering, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Multi-dimensional metabolic engineering and enzyme engineering in Escherichia coli for highly efficient biosynthesis of 2,5-furandicarboxylic acid - Yanan Cui; Peiyi Zhang; Renjie Miao; Mengqi Zhao; Liqiang Fan; Xu Li; Yongjun Qiu; Chen Deng; Liming Zhao (Bioresource Technology, 2026)

Curcumin maintains pseudorabies virus latent infection by inhibiting the phosphorylation level of EGFR protein - Yuhang Li; Fan Yang; Dingqiu Zou; Pei Liu; Kexin Qi; Jingyi Wang; Chenlu Sun; Yanru Tang; Ruihan Zhang; Junyan Ren; Zijie Cui; Ruoxian Li; et al. (Veterinary Microbiology, 2026)

A numerical study of the possible influence of the ice nucleation process on the bolt-from-the-blue lightning production - Qianwei Zhao; Zheng Shi; Yanfeng Fan; Xuedong Cui; Haochen Chen; Wenzhong Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Acceleration of lattice oxygen induced by transitional metal doping in Fe3O4 via quenching strategy towards boosting toluene and chlorobenzene oxidation - Wenbo Xue; Juexiu Li; Huandan Cui; Yige Xi; Huifan Zheng; Ziqiang Li; Chuanyi Fan; Kajia Wei; Zhongxian Song; Jinping Jia (Fuel, 2026)

Structural property and bioactivity evaluation of reactive oxygen species hydrogels loaded with different polyphenols - Ya Fan; Shengrong Duan; Haiyan Zhang; Chushou Li; Guiguang Cheng; Tianqi Cui (Food Chemistry, 2026)

Influence of enzymatic modification on the structure–function properties of wheat bran arabinoxylan enriched fractions: Interplay of molecular weight and branching degree - Mohsin Rasheed; Boli Guo; Xiangqi Fan; Yingquan Zhang; Bo Zhang; Ming Li; Yutong Cui (Food Bioscience, 2026)

Guava polysaccharides as prebiotic candidates: selectively modulating microbiota in diseased gut environments to enhance epithelial regeneration - Weichen Liu; Haoyang Nian; Shaoqiang Fan; Yaqi Li; Qingdan Zheng; Li Cui; Liya Li; Xiaoyan Pang (Food Bioscience, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Modification of Ce−Fe oxide by quenching induced trace Sn doping for accelerating chlorobenzene oxidation - Juexiu Li; Wenbo Xue; Huandan Cui; Yige Xi; Rui Zhao; Yin Liu; Zhongxian Song; Kajia Wei; Ziqiang Li; Chuanyi Fan; Kan Li; Jinping Jia (Chemical Engineering Journal, 2026)

Prediction of energy consumption and carbon emission in Yunnan Province based on LEAP modeling - Zhengyuan Fan; Jie Yu; Taiwei Gu; Cui Qiao; Shaoyuan Li; Lin Ma; Wenhui Ma (Utilities Policy, 2026)

Green and efficient maize varieties synergize global yield and nitrogen sustainability - Xun Wei; Yulong Yin; Xueqin Zhu; Ziwen Li; Zhenying Dong; Yan Long; Yanbo Wang; Jiuran Zhao; Changling Huang; Xingming Fan; Huabang Chen; Pervez H. Zaidi; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Corrigendum to “Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process” [Process Safety and Environmental Protection 203 (2025) 107862] - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2026)

Acute topical menthol application and exercise performance: A systematic review and meta-analysis of perceptual and physiological responses - Yong Wang; Xiaohan Fan; Hansen Li; Xing Zhang; Mingyue Yin; Kai Xu; Yuming Zhong; Yilin Zhang; Juan Cui; Tianyu Song; Ping Liu; Hengzhi Deng (Journal of Thermal Biology, 2026)

Starch coating on low-sodium salt via fluidized bed granulation: Sensory improvement and health benefits - Xinyu Song; Xing Li; Xiangyu Liu; Zhaoxiang Ma; Zhi Fan; Zhiqiang Cui; Hui Xiong; Zhixin Li; Ying Zhou; Mingchun Lv; Yuan Li (Carbohydrate Polymers, 2026)

Genotypic features of Spinocerebellar Ataxia in Northern China: A Comparative Analysis with Southern China - Bin Chen; Songtao Niu; Xingao Wang; Yutin Ren; Fan Jian; Yuzhi Shi; Hongfei Tai; Hengheng Wang; Zhan Wang; Tao Cui; Wei Li; Hua Pan; et al. (The Cerebellum, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

CFSS strut system: A prefabricated method with low-carbon, economic and safety performance in deep excavation - Xuesong Cheng; Chenkai Li; Fan Yi; Qinghan Li; Jiqing Zhang; Peng Zhang; Tao Cui; Bo Li (Transportation Geotechnics, 2026)

Emitter flow rate of drip irrigation regulates the distribution and bioaccumulation of typical PPCPs in reclaimed wastewater-irrigated soil-plant systems - Jing Jin; Songjing Li; Erping Cui; Chao Hu; Shengshu Li; Zhenchao Zhou; Bingjian Cui; Chuncheng Liu; Junying Chen; Ge Gao; Xiangyang Fan (Journal of Environmental Sciences, 2026)

Bioconcentration kinetics and underlying mechanisms of tire additives and their transformation products in the fry stage of rainbow trout (Oncorhynchus mykiss) - Mengdi Wang; Hongliang Jia; Jingjing Sun; Danli Luo; Xiaofang Che; Song Cui; Zhaowei Wang; Yi-Fan Li (Environmental Pollution, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Reconstructing 150 years of land-use history in an alpine-deep lake: A high-resolution multi-proxy sediment record from Fuxian Lake, China - Fan Xu; Sidan Cui; Jinhao Dong; Sihan Li; Yawen Ge; Wenlei Luo; Yuecong Li (CATENA, 2026)

Paeoniflorin's role in inhibiting malignant metastasis of gastrointestinal stromal tumors via CYP3A4 modulation - Dapeng Cui; Zeyin Cui; Yansen Li; Shuang Fan; Lei Li; Cheng Yang; Ruixia Yu; Jiaxin Cui; Runjia Fu; Jiandong Fei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Characterization of laccase genes from apple varieties: structural and kinetic variations - Jinyang Li; Yinjun Fan; Mengxia Cui; Ziwen Teng; Fanglong Chen; Xuechao Zhang; Shengjun Zhang; Fanghao Wan; Hongxu Zhou (Journal of Plant Biochemistry and Biotechnology, 2026)

Mume Flos ameliorates MASLD-associated cognitive impairment by attenuating IL-17/NF-κB-mediated metabolic neuroinflammation - Shuqin Cui; Yali Wang; Qi Zhang; Hongyun Li; Wanting Hu; Fan Yang; Wei Zhang; Jinmei Ou (Metabolic Brain Disease, 2026)

Coupled dynamics and resonance mitigation of submerged floating tunnel roadways under transient impact loads in marine environments - Xiaolu Cui; Jing Chen; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong; Pupeng Ai; Shixiao Fan (Ocean Engineering, 2026)

Ball-milling induced boosting catalytic oxidation of volatile organic compounds - Huandan Cui; Juexiu Li; Yige Xi; Wenbo Xue; Shixiang Lu; Yifan Wang; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Journal of Environmental Chemical Engineering, 2026)

Stop “test-and-see”: The evolved need for translational safety assessment in pharmaceutical biomaterials - Yujian Fan; Xiaokai Guo; Jiaying Lyu; Tianyang Huang; Caibin Zhang; Xinyu Wang; Xiaolin Cui; Chenzhong Li; Yisheng He (Chemical Engineering Journal, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Comparative Analysis of Sensory Quality and Microbial Communities Between Medium–High- and High-Temperature Daqu From Shangqiu Region - Mengjun Cui; Yurong Wang; Jixiang Sun; Jun Zhang; Haibao Fan; Yanju Li; Zhuang Guo; Huijun Zhao (Current Microbiology, 2026)

Occurrence and dietary risk assessments of polyethoxylated tallow amine in soybeans - Xinru Cui; Zhenjun Liu; Rui Yang; Minjie Li; Xinru Guo; Zixuan Liu; Ziqian Xue; Bei Fan; Zehua Ke; Chunmei Li; Fengzhong Wang (Journal of Hazardous Materials, 2026)

Concurrent biodegradation of tylosin and tilmicosin by a novel Paracoccus versutus 4-B-2 - Zhengyan Chen; Anqi Liu; Junzhe Cui; Chunhui Liu; Huijuan Li; Ziyi Quan; Yaxu Liu; Xiao Guo; Xiaoyu Wang; Liling Fan; Bo Wang (Journal of Hazardous Materials, 2026)

Loofah-inspired recyclable MXene/polypyrrole fiber-skeleton hydrogels for machine-learning-assisted multimodal flexible sensor - Zhiyang Li; Chendan Cui; Fan Yang; Di Yuan; Hemiao Wang; Zhaoyun Lin; Lupeng Shao; Qiang Wang; Weikun Jiang; Linglong Shi; Yu Liu; Dehai Yu (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

SynPER: Synthesized prioritized experience replay for USVs formation control in island-reef waters via multi-agent reinforcement learning - Zijian Hu; Jiangyong Jin; Yani Cui; Bo Li; Jia Ren; Fan Yang (Ocean Engineering, 2026)

A new dameselloid trilobite from the Changhia Formation (Cambrian, Drumian) in central Shandong, North China - Guang-Ying Ren; Jin-Liang Yuan; Yi-Fan Wang; Bai-Zheng An; Kai Chen; Xiao-Hui Cui; Jian Gao; Nan Li (Palaeoworld, 2026)

Hierarchically reinforced hydrogel nonwoven dressings based on carboxymethyl cellulose and silver-loaded chitosan fibers for enhanced diabetic wound healing - Sijia Fan; Yungang Hu; Xueqin Wang; Jiashen Li; Lu Yu; Aihua Cui; Yuming Shen; Zhenghai Qu; Bin Wang; Jiwei Li (Chemical Engineering Journal, 2026)

Dissecting the aberrant vasculature of glioblastoma: mechanisms and therapeutic targets - Yinan Li; Yinfei Du; Fan Guan; Xuetong Li; Shu Cui; Wei Gao; Xinmiao Long; Minghua Wu (Cancer and Metastasis Reviews, 2026)

The paleoclimatic footprint in the terrestrial net primary productivity of the northern Tibetan Plateau - Anning Cui; Jianping Zhang; Xingqi Liu; Deke Xu; Hao Li; Baoshuo Fan; Houyuan Lu (Review of Palaeobotany and Palynology, 2026)

Modulation mechanism of starch gelatinization and gluten network restructuring in wheat flour during atmospheric steam treatment - Xiangqi Fan; Jikai Jiang; Mohsin Rasheed; Ming Li; Yingquan Zhang; Yutong Cui; Bo Zhang; Boli Guo (Food Hydrocolloids, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Isolating a novel quorum quenching strain based on carbon source adaptability for bioaugmentation under different carbon source conditions - Jun Li; Yanan Cui; Fan Yang; Yanxue Pei; Muchen Yin; Chaofan Xie; Yaodong Wu (Bioresource Technology, 2026)

Impact of Madden–Julian Oscillation on the forecast of marine heatwaves in the southeastern tropical Indian ocean - Zhanxian Cui; Yuanlong Li; Yangke Liu; Qing Bao; Lei Zhang; Kai Ge; Fan Wang (Climate Dynamics, 2026)

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Enhanced nitrogen removal in a micro-polluted drinking water reservoir by a new WLA-Bio® system: Mechanisms and applications - Cihang Yan; Hongchao Hou; Nan Li; Fan Si; Yexinglong Jiao; Chao Liu; Tao Cui; Haihan Zhang; Tinglin Huang (Water Research, 2026)

Active packaging based on nanocellulose-stabilized essential oil pickering emulsions: A review on enhanced properties and food preservation applications - Fan Li; Mengmeng Pang; Kun Liu; Shasha Lv; Quanfen Guo; Peide Cui; Wanqing Lei; Wei Liu; Xing Zhou; Ting Xu; Chuanling Si (Trends in Food Science & Technology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

A large manta ray-inspired bio-robotic platform for deep-sea exploration from laboratory to 2000-m depths - Qimeng Liu; Qu He; Weikun Li; Pengming Guo; Jie You; Weicheng Cui; Dixia Fan (Ocean Engineering, 2026)

Effect of the typical coal ash-analogous minerals on the migration of heavy metals during coal combustion - Mengzhu Yu; Jingwen Chen; Zhicheng Zhu; Yaji Huang; Pu Yang; Hao Xu; Menghui Li; Lu Tang; Xihui Fan; Yifan Xu; Dongxu Cui (Fuel, 2026)

Iron and platinum alternating active sites for efficient photocatalytic overall water splitting - Yanfei Fan; Yan Liu; Ying Liang; Kang Chen; Qingqing Li; Dongxu Pan; Shiqiu Zhang; Guanwei Cui; Bo Tang (Chemical Engineering Journal, 2026)

A 25,000-yr-long integrated large earthquake record of the Xiaojiang Fault zone, southeastern Tibetan Plateau: New paleoseismic evidence from Yangzong Lake - Jiawei Fan; Fangming Zhang; Hanchao Jiang; Hongyan Xu; Minggang Cai; Kai Cui; Dayou Zhai; Changfei Jin; Kai Li; Wei Shi; Xiaotong Wei; Ning Zhong; et al. (Science China Earth Sciences, 2026)

Longitudinal biomarker trajectories and their prognostic utility for 21-day mortality in burn patients with sepsis: a retrospective cohort study - Jiaqi Lou; Hong Kong; Jiliang Li; Ziyi Xiang; Xiaoyu Zhu; Shengyong Cui; Neng Huang; Sida Xu; Guoying Jin; Xin Le; Youfen Fan (Inflammation Research, 2026)

In–situ aquaculture treatment: Co–addition of autotrophic and heterotrophic bacteria with biodegradable polymers (PHBV) to Penaeus vannamei culture systems - Kai Luo; Liang Cui; Mingyang Wang; Yumeng Xie; Mingjing Li; Yunhui Liu; Tengfei Li; Ruiyong Fan; Xiangli Tian (Aquaculture, 2026)

Neolithic genomes reveal long distance interactions in agropastoral border zone of Yan Mountain Region - Daxuan Zhang; Bing Sun; Fajun Li; Xue Zhao; Zhanhu Zhao; Jun Li; Shizhu Gao; Yu Li; Qiankun Quan; Natalia Berdnikova; Ivan Berdnikov; Shan Chen; et al. (Science Bulletin, 2026)

Response mechanisms of spatial ecological patterns in the Yellow River estuary to water-sediment regulation scheme - Shouwen Qiao; Yongqing Yu; Linfeng Wang; Mingming Zhu; Xiang Zheng; Xiuxia Wang; Guangxin Cui; Fan Li; Yanyan Yang (Regional Studies in Marine Science, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Inactivation of Penicillium ochrochloron spores by pulsed light: Mechanism and preservation efficacy in strawberries - Xiaozhen Cui; Anthony Pius Bassey; Fan Wang; Shudong Xie; Dongnan Li; Linlin Fan; Yongsheng Zhu; Li Bin; Xiaoli Liu (Food Control, 2026)

miR-23a modulates chlorantraniliprole susceptibility by targeting SfGSTs3 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Yong-Po Lv; Bai-Zhong Zhang; Meng-Yuan Zhang; Ling-Ling Cui; Ren-Jie Li; Dong-Mei Chen; Yu-Yang Peng; Run-Qiang Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

The comprehensive fingerprints of VOCs from complex coking emissions and their temporal evolution in the atmosphere based on backward inference method - Hongyan Li; Shidan Huang; Yuanchun Ren; Yanru Zhang; Jing'’ai Bai; Hongyu Li; Guozhong Zhang; Xueying Gao; Yang Cui; Lili Guo; Jie Fan; Yongchun Liu; et al. (Atmospheric Research, 2026)

Redox and Bioenergetic Modulation by Acacetin Attenuated Neuropathic Allodynia in Mice with Diet-induced Diabetes - Youya Fan; Weibo Zhou; Zhengyao Zhu; Benling Li; Wugeng Cui; Xin Zhao (Molecular Neurobiology, 2026)

Neural network approaches for enhanced nitrate management in recirculating aquaculture systems - Xiangyu Fan; Jiaxin Li; Zhengguo Cui; Shengkang Liang; Jianlei Chen; Hongwu Cui; Hao Li; Yong Xu; Zhengdong Yin (Aquacultural Engineering, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Optimizing flapping foil dynamics: A data-driven framework for motion optimization - Jinyu Li; Ruipeng Li; Jiaye Gong; Weicheng Cui; Dixia Fan (Ocean Engineering, 2025)

Recycled oceanic crust restricting trace element enrichment in mid-ocean ridge basalts - Fan Yang; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Peng-Li He; Le Zhang; Ze-Xian Cui (Lithos, 2025)

Capture and release methods of extracellular vesicles based on functional magnetic beads - Zeying Liu; Ziwei Lu; Ying Li; Yichun Fan; Wenwen He; Yali Cui (Chemical Engineering Journal, 2025)

From materials-biology micro-interface to critical genes: Dissecting bio-hybrid-driven heterogeneous Fenton process for enhanced pollutant degradation - Hao Sun; Cui Lai; Ling Li; Zhexin Chen; Mingming Zhang; Fuhang Xu; Xuerong Zhou; Xiuqin Huo; Dengsheng Ma; Huchuan Yan; Xiaorui Hu; Xing Fan; et al. (Chemical Engineering Journal, 2025)

A Bilevel Programming Model for China’s Cross-border Forestry Carbon Sink Planning Considering Regional Collaboration Strategy - Changmin Li; Yuan Fan; Na Cui; Xiaoqiang Xie (Small-scale Forestry, 2025)

Serum amyloid A: multifaceted roles in inflammation and cellular interactions - Shouzheng Cheng; Dingyu Duan; Hao Cui; Yingying Lian; Fan Jiang; Qianming Chen; Taiwen Li; Lei Zhao (Immunologic Research, 2025)

Inversion of the Deep Structure of the Northern Margin of the Ordos Block Using Teleseismic Receiver Functions and Gravity Data - Feng-Zhi Cui; Fan Zhang; Juan Li; Dong-Yang Pei; Yi-Hang Bai; Lei Wang; Hui Wang (Applied Geophysics, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

Water erosion shapes deformation in alpine meadow patches on the Qinghai-Tibetan Plateau - Lirong Zhao; Kexin Li; Suyuan Jia; Zeng Cui; Yi-Fan Liu; Shixiong Li; Xiaoli Wang; Nufang Fang; Yu Liu (Soil and Tillage Research, 2025)

Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2025)

Diatomite/polyaniline-BiOCl functionalized hierarchical composite membranes for simultaneous photothermal interface water evaporation and wastewater purification - Mengyang Cui; Jiaqing Xu; Jinrui Li; Yimeng Fan; Cuijiao Mao; Jianhui Sun; Xianfa Su; Yunqing Pi; Shuying Dong (Journal of Environmental Management, 2025)

Evolution of phosphorus during co-pyrolysis of wheat straw and mulch film components - Chao Fan; Junxia Wang; Yuxin Yang; Jian Li; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Chemical Engineering Journal, 2025)

Mg/Mn co-doped carbon dot nanozyme with high superoxide dismutase-like activity and fluorescence for transdermal therapy of atopic dermatitis - Yu Zhang; Jinyu Shi; Xiangyang Fang; Jing Li; Xing Fan; Ke Wang; Guoqiang Gao; Fufang Luo; Na Xu; Zhining Xia; Cui Liu (Chemical Engineering Journal, 2025)

A Facile-Synthesized Dual-Network Multi-Ionic Integrated Explosive with Enhanced Detonation Performance and Promoted Aluminum Reactivity - Yun-Fan Yan; Yu Shang; Ming-Yu Guo; Shao-Li Chen; Meng Cui; Zhi-Hong Yu; Wei-Xiong Zhang; Xiao-Ming Chen (Chemical Engineering Journal, 2025)

Bacterial communities and C N cycling drive microplastic-specific trade-off between greenhouse gas emissions and antibiotic resistance genes during reductive soil disinfestation - Yanlong Chen; Fengyang Zhang; Yuhan Zhang; Risheng Xu; Jingyi Mei; Kun Wang; Cui Li; Fan Chen; Yuheng Wang (Applied Soil Ecology, 2025)

Pollen-vegetation-climate relationships in different steppe types of North China: implications for Quaternary reconstructions of vegetation and climate - Yongjie Zhao; Fan Xu; Sidan Cui; Xin Mao; Gaolei Jiang; Ruchun Zhang; Linjing Liu; Yawen Ge; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mechanistic insights into H2O2 activation by high-density iron single-atom catalysts for efficient water treatment: Surface-bound radical and singlet oxygen - Fuhang Xu; Cui Lai; Mingming Zhang; Zuying Yao; Dengsheng Ma; Bisheng Li; Meng Qin; Huchuan Yan; Xiuqin Huo; Xing Fan; Biting Wang; Shiyu Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

The role of potassium in lode gold mineralization: insights from ab initio molecular dynamics and geochemical modeling - Gao-Hua Fan; Jian-Wei Li; Yuan Mei; Si-Yu Hu; Ri-Chen Zhong; Chang Yu; Xiao-Dong Deng; Hao Cui; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Spear and shield in the design of cream-type MgH2 for hydrolytic hydrogen production - Zhendong Yao; Wenqing Li; Xuepeng Liu; Jianbo Chen; Chao Li; Yican Chu; Jinlong Cui; Leichao Meng; Yongfu Cui; Meiqiang Fan (Fuel, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Shrub encroachment and degradation impact water balance by altering water fluxes in alpine meadows - Lirong Zhao; Kexin Li; Nufang Fang; Suyuan Jia; Zeng Cui; Yi-Fan Liu; Shixiong Li; Xiaoli Wang; Yu Liu (CATENA, 2025)

Highly efficient conversion of androstenedione into dehydroepiandrosterone through the construction of molecular machines - Minjie Li; Xiaojun Wang; Yue Fan; Xuemei Li; Yunfeng Cui; Liangyan Zhu; Xiangtao Liu; Xi Chen; Na Liu; Yanbing Shen; Jinhui Feng; Jinku Bao; et al. (Systems Microbiology and Biomanufacturing, 2025)

Hormetic effect of dissolved organic matter from pig manure anaerobic digestion effluents on Chlorella sp.: Physiological and transcriptomic responses - Zhiqiang Gu; Yuhuan Liu; Liandong Zhu; Boyou Fan; Yuan Li; Cuixia Liu; Yunpu Wang; Xian Cui; Zhigang Yu; Roger Ruan; Qi Zhang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Magic cube metamaterials - Zuntian Chu; Xinqi Cai; Ruichao Zhu; Tonghao Liu; Huiting Sun; Fan Wu; Tiefu Li; Yuxiang Jia; Yajuan Han; Shaobo Qu; Tiejun Cui; Jiafu Wang (Science Bulletin, 2025)

The core cellular network modulates immune phenotype switching in hepatitis B - Chuangeng Chen; Ziqi Zhen; Meng Cui; Xiaoli Hu; Lei Yu; Fengxia Zhou; Xiaorong Yu; Dehui Yang; He Wu; Ying Cui; Xiang Li; Xudong Cui; et al. (Science Bulletin, 2025)

Retraction Note: Effect of Danhong injection on pharmacokinetics and pharmacodynamics of rivaroxaban in rats - Weihong Yin; Jiao Li; Zhaoyang Han; Siwen Wang; Fan Wu; Chao Yu; Xueying Yan; Mingyu Cui (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Effective Purging and Conservation of Heterozygous Regions During Independent Evolution to High‐Level Inbreeding in Wild Paradise Fishes - Zhongxing Wang; Dongji Yao; Benchi Zhao; Yi Shao; Fan Li; Ka Yan Ma; Rongfeng Cui (Molecular Ecology, 2025)
Inbreeding may initially lower population fitness by converting masked genetic load into realised load. As deleterious variants become increasingly homozygous, purifying selection acts more effectively to purge load. Nevertheless, not all populations can survive the initial fitness decline, and it would be interesting to examine scenarios that facilitate their survival. Herein, we assembled chromosome‐level reference genomes of two paradise fishes, Macropodus hongkongensis and M. opercularis , and resequenced 109 wild individuals of 15 populations to infer the history of runs of homozygosity (ROH) formation, effectiveness of purging in ROH, and the role of balancing selection in maintaining lingering polymorphisms in independently evolved small populations. While the two species diverged in genes potentially adaptive to their local niches, there were large variations in inbreeding coefficients and the amount of genetic load within species. Three populations became highly inbred ( F ROH > 0.50) from independent origins. Simulations showed that the ROH segment size distribution can be best explained by living in a small population for hundreds, if not thousands, of generations. The genetic load negatively correlated with summed ROH length. This was driven by more effective purging in ROH. The non‐ROH regions between individuals from different high‐ F ROH populations were repeatable, with nearby signals of balancing selection persisting in the polymorphic genomic regions through species divergence.

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Cold atmospheric plasma-activated liquid inhibits peritoneal metastasis in drug-resistant ovarian cancer by targeting the epithelial-mesenchymal transition - Jinren Liu; Xiangni Wang; Yixin Cui; Jiajia Lu; Zhirou He; Yulin Xu; Rongrong Li; Guimin Xu; Lingge Gao; Xiaolin Fan; Xili Wu; Xingmin Shi; et al. (Clinical & Experimental Metastasis, 2025)

Recent Progress on Underwater Wireless Communication Methods and Applications - Zhe Li; Weikun Li; Kai Sun; Dixia Fan; Weicheng Cui (Journal of Marine Science and Engineering, 2025)
The rapid advancement of underwater wireless communication technologies is critical to unlocking the full potential of marine resource exploration and environmental monitoring. This paper reviews recent progress in three primary modalities: underwater acoustic communication, radio frequency (RF) communication, and underwater optical wireless communication (UWOC), each designed to address specific challenges posed by complex underwater environments. Acoustic communication, while effective for long-range transmission, is constrained by ambient noise and high latency; recent innovations in noise reduction and data rate enhancement have notably improved its reliability. RF communication offers high-speed, short-range capabilities in shallow waters, but still faces challenges in hardware miniaturization and accurate channel modeling. UWOC has emerged as a promising solution, enabling multi-gigabit data rates over medium distances through advanced modulation techniques and turbulence mitigation. Additionally, bio-inspired approaches such as electric field communication provide energy-efficient and robust alternatives under turbid conditions. This paper further examines the practical integration of these technologies in underwater platforms, including autonomous underwater vehicles (AUVs), highlighting trade-offs between energy efficiency, system complexity, and communication performance. By synthesizing recent advancements, this review outlines the advantages and limitations of current underwater communication methods and their real-world applications, offering insights to guide the future development of underwater communication systems for robotic and vehicular platforms.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Impact of freshwater discharges on the abundance and spatial distribution of moon jellyfish (Aurelia aurita) in Yellow River Estuary, China - Xiaomin Zhang; Bingqing Xu; Guangxin Cui; Xiuxia Wang; Haixia Su; Shaowen Li; Yanyan Yang; Xiang Zheng; Fan Li (Journal of Environmental Management, 2025)

Cr (VI) induces lactate utilization through HIF-1α/MCT1 dependent on p53 protein level - Shengnan Li; Yajing Guo; Xiaojing Cui; Li Li; Jianhui Fan; Jun Cao (Food and Chemical Toxicology, 2025)

Vinylidene carbonate drived ultra-stable artificial SEI for lithium metal anode with ultra-long life - Fan Ding; Shuai Liu; Hao Xu; Zhiang Li; Zhenhua Yan; Hongzhi Cui (Chemical Engineering Journal, 2025)

LINC-p21 Regulates Pancreatic β-Cell Function in Type 2 Diabetes Mellitus - Zengkun Qian; Fan Cui; Zheng Mao; Zhen Li; Xiayu Yi; Jingjing Zhou; Jinjin Cao; Xiaoqin Li (Biochemical Genetics, 2025)

Biocontrol effects of volatile organic compounds released from Burkholderia sola NAU20 to strawberry anthracnose caused by Colletotrichum gloeosporioides - Dongming Wang; Zhitao Geng; Jiming Shen; Tingting Xie; Fan Wu; Yu Zhang; Yiwei Dong; Dongmei Mao; Yanling Ji; Yan Huang; Zhoukun Li; Yongheng Liang; et al. (Postharvest Biology and Technology, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Pectoral Fin-Assisted Braking and Agile Turning: A Biomimetic Approach to Improve Underwater Robot Maneuverability - Qu He; Yunpeng Zhu; Weikun Li; Weicheng Cui; Dixia Fan (Journal of Marine Science and Engineering, 2025)
The integration of biomimetic pectoral fins into robotic fish presents a promising approach to enhancing maneuverability, stability, and braking efficiency in underwater robotics. This study investigates a 1-DOF (degree of freedom) pectoral fin mechanism integrated into the SpineWave robotic fish. Through force measurements and particle image velocimetry (PIV), we optimized control parameters to improve braking and turning performances. The results show a 50% reduction in stopping distance, significantly enhancing agility and control. The fin-assisted braking and turning modes enable precise movements, making this approach valuable for autonomous underwater vehicles. This research lays the groundwork for adaptive fin designs and real-time control strategies, with applications in underwater exploration, environmental monitoring, and search-and-rescue operations.

Effects of calcium-sensitive receptors on chondrogenic differentiation of rat bone marrow mesenchymal stem cells - Siyu Li; Xiang Jia; Yongping Cui; Kainan Liu; Tianjie Xu; Jiaxin Fan; Hui Zhang; Yueyuan Li; Qian Wang (Cell and Tissue Banking, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Identification of alternative splicing transcripts of Dorsal from Procambarus clarkii and their roles in innate immunity - Ying Huang; Rui Shen; Li-Fan Cui; Qian Ren (Aquaculture, 2025)

The effect of the aging processes of Ulva prolifera-derived dissolved organic nitrogen associated with green tide on the diatoms-dinoflagellates succession in the Southern Yellow Sea, China - Xinyu Li; Cui Zeng; Xiurong Han; Liqiang Fan; Jing Zhao; Yingzhe Wang; Xiulin Wang; Keqiang Li (Water Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Analysis of seepage and hysteresis effect mechanism of unsaturated loess based on resistivity test - Bo Cui; Tianfeng Gu; Jiading Wang; Jiacheng Li; Nannan Fan; Xin Li; Zhijie Song; Min Hao (Journal of Hydrology, 2025)

RIG-I-driven CDKN1A stabilization reinforces cellular senescence - Cui Wang; Xiaoyu Jiang; Hong-Yu Li; Jianli Hu; Qianzhao Ji; Qiaoran Wang; Xiaoqian Liu; Daoyuan Huang; Kaowen Yan; Liyun Zhao; Yanling Fan; Si Wang; et al. (Science China Life Sciences, 2025)

Community structure and selected genes abundance shift of rhizosphere and endophyte bacteria from roots associated with the sludge application under reclaimed water irrigation - Bingjian Cui; Haishu Sun; Erping Cui; Chao Hu; Xiangyang Fan; Zhongyang Li; Chuncheng Liu (Applied Soil Ecology, 2025)

Investigation of 1,3-Diketone and Nano-Copper Additives for Enhancing Boundary Lubrication Performance - Jingsi Wang; Dezhi Teng; Jiawei Fan; Xi Zhang; Qihang Cui; Ke Li; Pay Jun Liew (Journal of Marine Science and Engineering, 2025)
In this work, 1,3-diketone synthesized via the Claisen condensation method and nano-copper particles modified by the Brust–Schiffrin method were added into a commercial marine medium-speed diesel engine cylinder piston oil to evaluate their effects on boundary lubrication performance. Friction and wear tests conducted on CKS-coated piston ring and cast-iron cylinder liner samples demonstrated significant reductions in both friction and wear with the addition of 1,3-diketone and nano-copper particles. Compared to the original oil without additives, the friction force was reduced by up to 16.7%, while the wear of the piston ring and cylinder liner was decreased by up to 21.6% and 15.1% at 150 °C, respectively. A worn surface analysis indicated that the addition of 1,3-diketone and functionalized nano-copper particles influenced the depolymerization and tribo-chemical reactions of the anti-wear additive ZDDP (zinc dialkyldithiophosphate) in the original engine oil. This modification enhanced the oil’s anti-friction and anti-wear properties, offering valuable insights into the development of eco-friendly lubricants for energy-efficient systems.

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Boosting the hydrogen storage performance of Mg-rich quaternary alloy hydrides via in-situ evolution of bidirectional catalytic phases - Ruijie Liu; Xinhao Jiang; Xinqiang Wang; Zhenglong Li; Xiaoying Yang; Jingbo Chen; Yanxia Liu; Wengang Cui; Fan Gao; Yong Gao; Fulai Qi; Chao Zheng; et al. (Chemical Engineering Journal, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Chaihu Guizhi Ganjiang Decoction ameliorates chronic pancreatitis by modulating the SK1/S1P signaling pathway - Guo-Wang Yao; Cai-Xia Li; Yu-Xing Fan; Yu-Zhen Zhuo; Shu-Kun Zhang; Li-Hua Cui (Journal of Natural Medicines, 2025)

Long-term monitoring of chloride deposition and its influencing factors around an island in the East China Sea - Jiannan Jia; Zhiqiang Cui; Yuanbei Li; Cong Liu; Qiang Xu; Xianping Fan (Acta Oceanologica Sinica, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Comparative study of the characteristics of the energy flow and food web structure in the Laizhou Bay ecosystem based on the Ecopath and LIM-MCMC models - Cui Wenhui; Xu Bingqing; Dong Xiuqiang; Yang Jisong; Li Min; Zhang Depu; Li Shengfu; Lv Zhenbo; Li Fan; Ren Zhonghua (Frontiers in Marine Science, 2025)
This study compared the characteristics of energy flow and food web structure in the Laizhou Bay ecosystem using the Ecopath model and linear inverse models enhanced by Monte Carlo methods coupled with a Markov Chain (LIM-MCMC), respectively, based on survey data collected in May, August, and November 2022. The ecosystem was divided into 22 functional groups with trophic levels ranging from 1.00 to 3.48 and a large proportion of predator groups. The Ecopath model estimated an overall energy transfer efficiency of 5.34%, with the detrital food chain exhibiting significantly higher energy transfer efficiency (6.73%) than the grazing food chain (5.31%). Energy flow paths in the LIM-MCMC model were classified into four primary routes, predominantly driven by respiration and the inflow of detritus at lower trophic levels, which accounted for 79.9% of the total energy flow in group a. The Ecopath model provided a connectance index of 0.30, a system omnivory index of 0.33, Finn’s mean path length of 2.46, and Finn’s cycle index of 8.18%, whereas the LIM-MCMC model produced an average path length of 2.78. Both models indicated a shorter food chain and low complexity of the food web. Total system throughput (TST) was estimated at 10,086.1 (Ecopath) and 10,968.0 t·km -2 a -1 (LIM-MCMC), with total respiration and total flows into detritus accounting for 41.2% and 51.1% of TST, respectively. The total primary production to total respiration ratios were 1.40 (Ecopath) and 0.86 (LIM-MCMC). Despite consistent ecosystem parameters across both models—total consumption (4,407.7 t·km -2 a -1 ), total primary production (3,606.4 t·km -2 a -1 ), and total biomas (151.0 t·km -2 a -1 )—the Ecopath model suggested a relatively mature ecosystem, whereas the LIM-MCMC model indicated that this ecosystem was in an unstable developmental stage with low energy utilisation efficiency of primary productivity

Optimizing membrane dehumidification performance: A comprehensive review of materials, modules and system - Yilin Liu; Junbao Fan; Jincai Su; Na Li; Xin Cui; Liwen Jin (Journal of Environmental Chemical Engineering, 2025)

Engineering wood-MOF networks to realize multilevel weak water interactions for highly-efficient solar water-power cogeneration - Haoran Li; Rongcui Fan; Fudong Zhang; Ziwei Cui; Tiantian Wu; Qing Huang; Fangyuan Kang; Yahui Cai; Qichun Zhang; Dan Tian (Chemical Engineering Journal, 2025)

Brain-targeted delivery of Acetyl-11-Keto-β-Boswellic acid with enhanced anti-inflammatory efficacy via blood-brain barrier peptide shuttle PepH3 - Na Cui; Tingting Fan; Liang Li; Wei Liu; Mingjie Li; Mukun Huang; Qianwen Wu; Jingwen Wang; Wenbin Zhang; Shengzheng Wang; Yi Ding (Chemical Engineering Journal, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

RETRACTED ARTICLE: Effect of Danhong injection on pharmacokinetics and pharmacodynamics of rivaroxaban in rats - Weihong Yin; Jiao Li; Zhaoyang Han; Siwen Wang; Fan Wu; Chao Yu; Xueying Yan; Mingyu Cui (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparing Surface Mass Balance and Surface Temperatures From Regional Climate Models and Reanalyses to Observations Over the Antarctic Ice Sheet - Xiaofeng Wang; Peter L. Langen; Rongxing Li; Gang Qiao; Xiaopeng Fan; Yinke Dou; Xiangbin Cui (International Journal of Climatology, 2025)
This article assesses the performance of surface mass balance (SMB) and surface temperature products from seven climate models (ERA5, MERRA2, HIRHAM5_ERA‐Interim, HIRHAM5_ERA5, MARv3.11, RACMO2.3p1 and RACMO2.3p2) to be used as inputs to firn densification models (FDMs), crucial for the whole Antarctic mass balance estimation. The evaluation compiles and utilises a new dataset combining existing observations with 184 stake SMB measurements in the Vostok region and two SMB radar transects in Blåskimen Island and Nivlisen Ice Shelf, significantly enhancing the AntSMB dataset. For temperatures at 10 m (T10), 992 observations are included, offering vastly improved spatial coverage. Compared with multi‐year SMB observations, RACMO2.3p1 and ERA5 align closely with observed SMB over the inland and the whole Antarctic, with ERA5 exhibiting superior alignment in coastal areas. However, in terms of temporal SMB variations, ERA5, RACMO2.3p2 and HIRHAM5_ERA‐Interim demonstrate the best consistency with observed SMB, with ERA5 excelling in regression slope comparisons. In our surface temperature evaluation, RACMO2.3p2 and ERA5 have a minimal mean bias from T10 over the whole Antarctic. RACMO2.3p2 performs well with few occurrences of deviations beyond ±3°C in coastal areas, while RACMO2.3p2 and HIRHAM5_ERA5 are both close to T10 in inland areas. In inter‐model SMB comparisons, ERA5, HIRHAM5_Interim, HIRHAM5_ERA5, RACMO2.3p1 and RACMO2.3p2 exhibit similar deviations from the multi‐model mean (MMM), while MARv3.11 and MERRA2 show larger deviations in some coastal areas. For surface temperature, MARv3.11 and ERA5 display larger deviations from the MMM in some coastal areas where ERA5 actually matches the observations well, illustrating that MMM should not be taken to represent the true climate conditions. In conclusion, ERA5 demonstrates the best overall consistency with SMB and T10 observations compared with the other models.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Endogenous stem cell repair strategy via electromechanical interaction for stress injury - Honglin Xiang; Fan Wang; Qing Zhang; Zeyu Han; Yefei Lei; Neng Lai; Ke Jiang; Hanfeng Yang; Wenguo Cui; Yuling Li (Chemical Engineering Journal, 2025)

A green biocatalyst fabricated by fungal laccase immobilized onto Fe3O4@polyaniline-chitosan nanofibrous composites for the removal of phenolic compounds - Hao Wang; Can Jin; Xin Li; Jin-Xin Ma; Yi-Fan Ye; Lu-Xin Tang; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effects of unsaturated C18 fatty acids on “glucose-glutathione” Maillard reaction: Comparison and formation pathways of initial stage and meaty flavor compounds - Wenbin Du; Qianli Ma; Yang Li; Shuang Bai; Yatao Huang; Weiye Cui; Cecilia Accoroni; Bei Fan; Fengzhong Wang (Food Research International, 2025)

Highly efficient CO2 capture from open air and dilute gas streams by tunable azolate ionic liquids based deep eutectic solvents - Guokai Cui; Yepin Cheng; Wei Zhang; Xiangyu Shen; Lai Li; Ruina Zhang; Yaoji Chen; Quanli Ke; Chunliang Ge; Huayan Liu; Wenyang Fan; Hanfeng Lu (Chemical Engineering Journal, 2025)

Bioaccumulation of novel brominated flame retardants in a marine food web: A comprehensive analysis of occurrence, trophic transfer, and interfering factors - Wenchao Yang; Zhaowei Wang; Yan Jiang; Song Cui; Meng Yang; Changhong Li; Yi-Fan Li; Hongliang Jia (Science of The Total Environment, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

Response of ammonium transformation in bioanodes to potential regulation: Performance, electromicrobiome and implications - Xin Tang; Qianjing Yao; Xiaodun Jiang; Chunlin Wang; Yang Liu; Cui Li; Yanlong Chen; Wenzong Liu; Fan Chen; Yuheng Wang (Bioresource Technology, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Emission inventory of IVOCs from diesel engine emissions in China based on real-world measured data - Han Yuanxin; Hou Xiaoxiao; Zhang Fan; Yan Caiqing; Li Jia; Cui Min (Science of The Total Environment, 2024)

Occurrence and distribution of phytic acid and its degradation products in soybeans in China: Analytical challenges - Jiayue Chen; Zhenjun Liu; Xinru Cui; Rui Yang; Xinru Guo; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2024)

Utilization of mycelial polysaccharide from Schizophyllum commune for the formation of highly stable o/w emulsion - Qi Meng; Qiong Wang; Jiahao Cui; Jinwei Li; Liuping Fan; Zhenghua Gu; Guiyang Shi; Lei Chen; Zhongyang Ding (Food Hydrocolloids, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Effects of Hydraulic Residence Time, NO3− and NO2− on Sulfate-Reducing Anaerobic Ammonium Oxidation Reaction - Siyu Shao; Li Cui; Danqi Wang; Juan Lu; Fan Qiu; Jia Bao; Xiaoxiong Song (Water, Air, & Soil Pollution, 2024)

Serine related gene CCT6A promotes metastasis of hepatocellular carcinoma via interacting with RPS3 - Hongwei Cui; Li Jiang; Yujiao Zhou; You Zhou; Fan Li; Zhenzhen Zhang (Functional & Integrative Genomics, 2024)

Synthesis of a novel β-cyclodextrin chiral stationary phase and its application to the evaluation of the enantioselective bioaccumulation and elimination behavior of tebuconazole in Rana nigromaculata tadpoles - Linbin Zheng; Meng Li; Zhouyu Jiang; Junyan Fan; Zengbo Fang; Jihuai Zheng; Yan Cui (Analytica Chimica Acta, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

A novel dual-detection electrochemiluminescence sensor for the selective detection of Hg2⁺ and Zn2⁺: Signal suppression and activation mechanisms - Huiting Hu; Zhaojiang Yin; Hanfeng Cui; Wei Xiong; Fengyao Yu; Jie Zhang; Fusheng Liao; Guobing Wei; Li Yang; Jing Zhang; Hao Fan (Analytica Chimica Acta, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Uncovering chromatin accessibility and cancer diagnostic potential via cell-free DNA utilization - Jie Li; Jiahui Chen; Xin Sun; Heli Yang; Keyong Sun; Chang Liu; Yongwang Wang; Mengyue Xu; Xin Ji; Ji Zhang; Xiaojiang Wu; Anqiang Wang; et al. (Science Bulletin, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Plasma-induced surface interactions of Pd/SrTiO3 catalyst for improved performance of photocatalytic degradation of toluene - Dongliang Gao; Bingwei Wang; Jingyue Bi; Fan Xue; Mifen Cui; Zhaoyang Fei; Lei Li; Xu Qiao (Journal of Environmental Chemical Engineering, 2024)

Imidacloprid removal by modified graphitic biochar with Fe/Zn bimetallic oxides - Song Cui; Jialin Lv; Rupert Hough; Qiang Fu; Zulin Zhang; Xiaolong Dong; Xiaohu Fan; Yi-Fan Li (Environmental Research, 2024)

Multimodal enhancement of ferroptosis for synergistic cascade colorectal cancer therapy - Ziying Wu; Kun Chen; Weisheng Mo; Yue Wang; Xiewei Lin; Zhien Lan; Caijing Mo; Haocheng Wang; Xiaoying Li; Xingdi Fan; Hungchen Chen; Zhilin Shu; et al. (Chemical Engineering Journal, 2024)

Mixed Eucalyptus plantations enhance soil organic carbon accumulation and chemical stability through soil microbial community and multifunctionality - Yaqin He; Chenyang Jiang; Rongyuan Fan; Yahui Lan; Han Zhang; Yuhong Cui; Linxin Li; Hao Wu; Shaoming Ye (CATENA, 2024)

Research progress on iron uptake pathways and mechanisms of foodborne microorganisms and their application in the food sector - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Jianrong Li; Tingting Li (Critical Reviews in Food Science and Nutrition, 2024)

Rheological Behavior and Microstructures in the Hybrid Gel of Scallop ( Patinopecten yessoensis ) Male Gonad Hydrolysates Modified by κ-Carrageenan and Methyl-β-Cyclodextrin - Wen Sun; Xiao-Fan Cui; Jia-Nan Yan; Xin-Yu Jiang; Lin Li; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2024)

Trophic transfer of dechloranes in marine food webs in Dalian Bay, China - Yan Jiang; Hongliang Jia; Wenchao Yang; Zhaowei Wang; Song Cui; Yi-Fan Li (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Plastic particles and fluorescent brightener co-modify Chlorella pyrenoidosa photosynthesis and a machine learning approach predict algae growth - Yaodan Dai; Zhi Guo; Xingpan Guo; Rui Deng; Lele Li; Ting Fan; Kangping Cui; Tao Pan (Journal of Hazardous Materials, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Bonding-slip behaviour of steel-concrete interfaces in CFDST members with PBL ribs - Yan-Li Shi; Jia-Xing Ren; Jia-Hao Fan; Wen-Da Wang; Hai-Cui Wang (Engineering Structures, 2024)

Satellite-based monitoring of China's above-ground biomass carbon sink from 2015 to 2021 - Hongqian Fang; Lei Fan; Philippe Ciais; Jingfeng Xiao; Rasmus Fensholt; Jingming Chen; Frédéric Frappart; Weimin Ju; Shuli Niu; Xiangming Xiao; Wenping Yuan; Jiangzhou Xia; et al. (Agricultural and Forest Meteorology, 2024)

Recent advances and prospects of neonicotinoid insecticides removal from aquatic environments using biochar: Adsorption and degradation mechanisms - Song Cui; Jialin Lv; Rupert Hough; Qiang Fu; LiHui An; Zulin Zhang; Yuxin Ke; Zhikun Liu; Yi-Fan Li (Science of The Total Environment, 2024)

A novel zwitterionic magnetic nanocomposite developed for non-invasive speciation analysis of inorganic chromium - Faisal Faiz; Yi-fan Pan; Sen Zhang; Jinxia Dai; Jun-qin Qiao; Hong-zhen Lian; Li Mao; Xiao-bing Cui (Journal of Hazardous Materials, 2024)

Butylparaben induces glycolipid metabolic disorders in mice via disruption of gut microbiota and FXR signaling - Haining Du; Lili Cui; Xinyi Zhao; Ziteng Yu; Tianyue He; Boya Zhang; Xingpei Fan; Meimei Zhao; Ruijiao Zhu; Ziyi Zhang; Mengcong Li; Jiaxin Li; et al. (Journal of Hazardous Materials, 2024)

Metal-organic frameworks derived low-cost Cu-doped Co3O4 for efficient reduction of ultra-low nitrate concentrations to ammonia - Xiaorui Hu; Mingming Zhang; Cui Lai; Min Cheng; Fuhang Xu; Dengsheng Ma; Ling Li; Huchuan Yan; Hao Sun; Xing Fan; Biting Wang (Chemical Engineering Journal, 2024)

Combination of Selenite and Butyrate Enhances Efficacy Against Colon Cancer by Targeting ASCT2-Mediated Amino Acid Metabolism - Jinling Cui; Jingsi Li; Shuang Zhao; Lihong Fan; Shutao Yin; Chong Zhao; Hongbo Hu (Biological Trace Element Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Effects of different thawing methods on physical and physicochemical properties of frozen dough and quality of corresponding steamed bread - Fan Zhang; Jinying Guo; Peiyao Li; Fen Zhao; Xue Yang; Qiaofen Cheng; J. Stephen Elmore; Ping Wang; Can Cui (Food Chemistry, 2024)

Super Fe3+ competing ability, high biocompatibility, and mild antibacterial carbon dots for food preservation - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Likun Ren; Qianqian Wang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Dominant role of the non‐forest woody vegetation in the post 2015/16 El Niño tropical carbon recovery - Lei Fan; Tianxiang Cui; Jean‐Pierre Wigneron; Philippe Ciais; Stephen Sitch; Martin Brandt; Xin Li; Shuli Niu; Xiangming Xiao; Jérome Chave; Chaoyang Wu; Wei Li; et al. (Global Change Biology, 2024)
The extreme dry and hot 2015/16 El Niño episode caused large losses in tropical live aboveground carbon (AGC) stocks. Followed by climatic conditions conducive to high vegetation productivity since 2016, tropical AGC are expected to recover from large losses during the El Niño episode; however, the recovery rate and its spatial distribution remain unknown. Here, we used low‐frequency microwave satellite data to track AGC changes, and showed that tropical AGC stocks returned to pre‐El Niño levels by the end of 2020, resulting in an AGC sink of Pg C year −1 during 2014–2020. This sink was dominated by strong AGC increases ( Pg C year −1 ) in non‐forest woody vegetation during 2016–2020, compensating the forest AGC losses attributed to the El Niño event, forest loss, and degradation. Our findings highlight that non‐forest woody vegetation is an increasingly important contributor to interannual to decadal variability in the global carbon cycle.

Functional Alpha and Beta Diversity of Fish Communities and Their Relationship with Environmental Factors in the Huanghe River (Yellow River) Estuary and Adjacent Seas, China - Shaowen Li; Yufang Huang; Fan Li; Yanfen Liu; Hongliang Ma; Xiaomin Zhang; Xiuxia Wang; Wei Chen; Guangxin Cui; Tiantian Wang (Fishes, 2024)
Fisheries and bottom seawater data were collected in July in 2022 and 2023 from 15 sampling stations in the Huanghe River estuary and adjacent seas in China. The patterns of functional alpha and beta diversity of fish communities in this area and their relationships with environmental factors were studied using trait-based analysis. Five functional classifications, which included 16 functional traits, four functional alpha diversity indices (functional richness, functional evenness, functional divergence, and community-weighted mean), three functional beta diversity indices (functional beta diversity and its turnover and nestedness components), and 14 bottom environmental factors were considered. The dominant traits of fish communities were the following: benthivorous feeding habits, small and front-facing mouths, high trophic level, demersal, anguilliform, low growth coefficient, medium resilience, low vulnerability, and adapted to warm temperate conditions. The dominant migration traits and types of fish eggs varied by year, and fish abundance was the main factor affecting the dominant traits of the communities. The results of multiple regression on distance matrices and variance partitioning analysis indicated that ammonia nitrogen content, total phosphorus content, and pH were the main environmental factors that affected fish functional diversity. The N/P ratio had a bottom-up control effect on fish functional diversity. Our findings also revealed that high pH gradients and distant geographical distances can inhibit trait turnover in fish communities.

A comparative analysis of growth and nutritional quality of the hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) in a simulated pond system and a recirculating aquaculture system - Yingsha Qu; Zhendong Yin; Xiangyu Fan; Haiyan Hu; Hongwu Cui; Zhengguo Cui; Keming Qu; Hao Li (Frontiers in Marine Science, 2024)
Groupers, as a popular economic fish species, are now more frequently cultured in land-based facilities, however, traditional pond-farming methods are plagued by frequent disease outbreaks, unstable economic benefits, and environmental pollution. To explore a new farming mode for a grouper, an 80-day cultivation experiment was conducted using both a simulated pond system (SPS) and a recirculating aquaculture system (RAS). The research aims to evaluate the growth performance, health (pathogenic bacteria, intestinal microbiota), off-flavor compounds (geosmin, 2-methylisoborneol), and nutritional component (amino acids, fatty acid composition and content) of a hybrid grouper ( Pinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ ) under different aquaculture systems. The results showed that the hybrid grouper in a RAS exhibited better growth performance; the concentration of Vibrio in the fish tissue in the RAS was significantly lower than that in the SPS. Moreover, the content of fresh amino acids in the RAS was significantly higher, and the levels of saturated fatty acids (SFAs) and ω-6 polyunsaturated fatty acids (ω-6PUFAs) were significantly higher in the RAS. This finding indicates the superior flavor and nutritional value of the grouper. These results prove that the RAS is suitable for the widespread cultivation of grouper.

STUB1 increases adiponectin expression by inducing ubiquitination and degradation of NR2F2, thereby reducing hepatic stellate cell activation and alleviating non-alcoholic fatty liver disease - Zheng Mao; Jindong Zhao; Fan Cui; Zhen Li; Jinjin Cao; Jingjing Zhou; Mingliang Hou; Zengkun Qian (Tissue and Cell, 2024)

Variations in plant root traits shaped by intraspecific interactions are species-specific - Shu Guo; Ka Ming Li; Min Liu; Weining Wang; Changhua Fan; Xingliang Xu; Xiaoyong Cui (Rhizosphere, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Linking bacterial life strategies with the distribution pattern of antibiotic resistance genes in soil aggregates after straw addition - Risheng Xu; Yuhan Zhang; Yue Li; Jianxiao Song; Yanru Liang; Fan Chen; Xiaomeng Wei; Cui Li; Wenbo Liu; Christopher Rensing; Yuheng Wang; Yanlong Chen (Journal of Hazardous Materials, 2024)

Resident water conservation behaviors among different age groups in rural areas of the Weibei arid belt, China - Xiaohu Dang; Aohua Li; Liangxin Fan; Junrui Cui (Journal of Cleaner Production, 2024)

Statistics of warm-season hourly extreme precipitation in the Sichuan Basin, China during 2002–2021 - Qin Li; Fan Wu; Shuai Yang; Xiaopeng Cui; Yong Zhang; Wulong Zhang (Theoretical and Applied Climatology, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Responses of different agricultural structures to nitrogen loss and agricultural green development in Northwest China - Jiaxin Liu; Xiangwen Fan; Xiuyuan Li; Yupin Zheng; Yan Li; Caixian Cui; Zhaohai Bai; Lin Ma; Bingnian Zhai; Ziyan Li (Agriculture, Ecosystems & Environment, 2024)

Design and validation of novel maize grain cleaning loss detection system based on classification models of particle time-domain signals - Yibo Li; Danielle S Tan; Tao Cui; Hongfei Fan; Yang Xu; Dongxing Zhang; Mengmeng Qiao; Yuxin Hou; Lijian Xiong (Computers and Electronics in Agriculture, 2024)

Assessment of the stabilization effect of ferrous sulfate for arsenic-contaminated soils based on chemical extraction methods and in vitro methods: Methodological differences and linkages - Ziqi Geng; Pengfei Wang; Naiyi Yin; Xiaolin Cai; Yaqi Fu; Chuanfang Fan; Xuhui Chang; Yunpeng Li; Jingnan Ma; Yanshan Cui; Peter E. Holm (Science of The Total Environment, 2024)

The introduction of influent sulfamethoxazole loads induces changes in the removal pathways of sulfamethoxazole in vertical flow constructed wetlands featuring hematite substrate - Erping Cui; Xiangyang Fan; Bingjian Cui; Shengshu Li; Taotao Chen; Feng Gao; Jianan Li; Zhenchao Zhou (Journal of Hazardous Materials, 2024)

Analysis of market risk volatility and warning in carbon trading market - Feng Dong; Zhicheng Li; Jue Cui; Yingxin Zhang; Bin Lu; Kai Fan; Kewei Xu; Jingyun Li; Jiaojiao Sun (Journal of Cleaner Production, 2024)

Laccase immobilization and its degradation of emerging pollutants: A comprehensive review - Hao Wang; Lu-Xin Tang; Yi-Fan Ye; Jin-Xin Ma; Xin Li; Jing Si; Bao-Kai Cui (Journal of Environmental Management, 2024)

Analysis of the effect of oat β-glucan on gut microbiota and clarification of their interaction relationship - Junying Bai; Chuan Zhang; Jie Cui; Mingcong Fan; Yan Li; Linhua Huang; Li Wang (Journal of Cereal Science, 2024)

Nutrient runoff and leaching under various fertilizer treatments and pedogeographic conditions: A case study in tobacco (Nicotiana tabacum L.) fields of the Erhai Lake basin, China - Chen Wang; Qi Miao; Zhibiao Wei; Yingxin Guo; Junying Li; Zhiyong Fan; Yanxia Hu; Hong Zhang; Junwei Sun; Zhenling Cui (European Journal of Agronomy, 2024)

Regulation of CuFeZn catalysts by K3PO4 and its effect on CO2 hydrogenation to C2+ alcohols - Sensen Zhou; Yueli Wen; Bin Wang; Maohong Fan; Lu Ren; Zheng Cui; Wei Huang; Jing Li; Jianping Guo (Chemical Engineering Journal, 2024)

Functional differentiation of olive PLP_deC genes: insights into metabolite biosynthesis and genetic improvement at the whole-genome level - Qizhen Cui; Qingqing Liu; Yutong Fan; Chenhe Wang; Yufei Li; Shuyuan Li; Jianguo Zhang; Guodong Rao (Plant Cell Reports, 2024)

The structure correspondence hypothesis predicts how word and sentence in language correlate with term and principle in mathematics - Jiaxin Cui; Liting Lv; Fan Yang; Lelei Wang; Jiarui Li; Zhanling Cui; Xinlin Zhou (Cognitive Processing, 2024)

Design and variable scale optimization of flare gas recovery process for hydrogen production - Wende Tian; Xiaomin Fan; Zhe Li; Zhe Cui; Bin Liu (Process Safety and Environmental Protection, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Soil microbial subcommunity assembly mechanisms are highly variable and intimately linked to their ecological and functional traits - Qiuping Fan; Kaifang Liu; Zelin Wang; Dong Liu; Ting Li; Haiyan Hou; Zejin Zhang; Danhong Chen; Song Zhang; Anlan Yu; Yongcui Deng; Xiaoyong Cui; et al. (Molecular Ecology, 2024)
Revealing the mechanisms underlying soil microbial community assembly is a fundamental objective in molecular ecology. However, despite increasing body of research on overall microbial community assembly mechanisms, our understanding of subcommunity assembly mechanisms for different prokaryotic and fungal taxa remains limited. Here, soils were collected from more than 100 sites across southwestern China. Based on amplicon high‐throughput sequencing and iCAMP analysis, we determined the subcommunity assembly mechanisms for various microbial taxa. The results showed that dispersal limitation and homogenous selection were the primary drivers of soil microbial community assembly in this region. However, the subcommunity assembly mechanisms of different soil microbial taxa were highly variable. For instance, the contribution of homogenous selection to Crenarchaeota subcommunity assembly was 70%, but it was only around 10% for the subcommunity assembly of Actinomycetes, Gemmatimonadetes and Planctomycetes. The assembly of subcommunities including microbial taxa with higher occurrence frequencies, average relative abundance and network degrees, as well as wider niches tended to be more influenced by homogenizing dispersal and drift, but less affected by heterogeneous selection and dispersal limitation. The subcommunity assembly mechanisms also varied substantially among different functional guilds. Notably, the subcommunity assembly of diazotrophs, nitrifiers, saprotrophs and some pathogens were predominantly controlled by homogenous selection, while that of denitrifiers and fungal pathogens were mainly affected by stochastic processes such as drift. These findings provide novel insights into understanding soil microbial diversity maintenance mechanisms, and the analysis pipeline holds significant value for future research.

Integration of spectral and image features of hyperspectral imaging for quantitative determination of protein and starch contents in maize kernels - Mengmeng Qiao; Tao Cui; Guoyi Xia; Yang Xu; Yibo Li; Chenlong Fan; Shaoyun Han; Jiaqi Dong (Computers and Electronics in Agriculture, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Comparative evaluation of soil accumulation of light stabilizers from biodegradable mulching films versus conventional polyethylene ones - Ruiqi Fan; Bingru Li; Qi Liu; Qiuyun Liu; Jixiao Cui; Runhao Bai; Yang Wang; Robert Elias; Cheng Li; Wenqing He (Journal of Hazardous Materials, 2024)

Experimental study on the flame-dual field overpressure coupling evolution characteristics of LPG/DME blended gas explosion venting - Gang Zhou; Yang Kong; Jianliang Yu; Qi Zhang; Runzhi Li; Dan Wang; Tao Fan; Yangyang Cui; Ziyuan Li (Journal of Cleaner Production, 2024)

Towards the co-benefits of carbon capture, utilization and sequestration: A life cycle assessment study for steel slag disposal - Zijie Li; Yi Xing; Mengying Ma; Wei Su; Yongkang Cui; Jinglei Tian; Fan Fei (Journal of Cleaner Production, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

Effects of anaerobic soil disinfestation on antibiotics, human pathogenic bacteria, and their associated antibiotic resistance genes in soil - Yanlong Chen; Yuhan Zhang; Risheng Xu; Jianxiao Song; Xiaomeng Wei; Xiaohui Liu; Cui Li; Fan Chen; Xiaohong Tian; Yuheng Wang (Applied Soil Ecology, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Satellite observed aboveground carbon dynamics in Africa during 2003–2021 - Mengjia Wang; Philippe Ciais; Rasmus Fensholt; Martin Brandt; Shengli Tao; Wei Li; Lei Fan; Frédéric Frappart; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; et al. (Remote Sensing of Environment, 2024)

Joint multi-objective optimization based on multitask and multi-fidelity Gaussian processes for flapping foil - Zhangyuan Wang; Yuqi Yan; Xinyu Zeng; Ruipeng Li; Weicheng Cui; Youzhi Liang; Dixia Fan (Ocean Engineering, 2024)

Coupling electrokinetic technique with hydrothermal carbonization for phosphorus-enriched hydrochar production and heavy metal separation from sewage sludge - Xutong Wang; Ondřej Mašek; Huwei Li; Fan Yu; Christian Wurzer; Junxia Wang; Beibei Yan; Xiaoqiang Cui; Guanyi Chen; Li'an Hou (Chemical Engineering Journal, 2024)

Study on the infection control performance under interactive cascade ventilation: A focus on a conference room environment - Han Li; Qiuyue Cui; Xiangfei Kong; Man Fan (Building and Environment, 2024)

Characteristics of polar organic compounds from diesel truck emissions measured by FT-ICR MS - Cui Min; Han Yuanxin; Yan Caiqing; Zhang Fan; Li Jun; Chen Yingjun (Atmospheric Environment, 2024)

Regulation of Hepatocellular Cholesterol Metabolism By Lactobacillus Paracasei BY2 and Its Embedding Delivery - Hua-Ling Cui; Meng-Fan Li; Sheng-Ya Liu; Ming Yu; Wen-Yong Lou (Probiotics and Antimicrobial Proteins, 2024)

The lack of homology domain and leucine rich repeat protein phosphatase 2 ameliorates visual impairment in rats with diabetic retinopathy through regulation of the AKT-GSK-3β-Nrf2 signal cascade - Li Chen; En Qi; Xuan Liu; Lijun Cui; Xiaojuan Fan; Ting Wei; Yaguang Hu (Toxicology and Applied Pharmacology, 2024)

Polyethylene upcycling to aromatics by pulse pressurized catalytic pyrolysis - Linyao Ke; Qiuhao Wu; Nan Zhou; Hui Li; Qi Zhang; Xian Cui; Liangliang Fan; Yuhuan Liu; Kirk Cobb; Roger Ruan; Yunpu Wang (Journal of Hazardous Materials, 2024)

Mechanism of interaction between astaxanthin and soy protein fibrils: Effects on complexes structure, rheological properties and bioaccessibility - Ning Li; Yi-fan Cui; Yi-an Liu; Mengyue Zhang; Yi-cheng Wang; Jiahui Shi; Xibo Wang; Ning Xu; Qingshan Chen (Food Hydrocolloids, 2024)

3D Printing windows and rheological properties for normal maize starch/sodium alginate composite gels - Ying Cui; Fan Yang; Chang-sheng Wang; Andreas Blennow; Changyong Li; Xingxun Liu (Food Hydrocolloids, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

High capillary effect and solar dual-drive nanofibrillated cellulose aerogels for efficient crude oil spill cleanup - Bingjie Fan; Xueming Bao; Shanshan Pan; Ying Liu; Yuanyuan Yu; Li Cui; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Structure evolution of porous alumina during aging process and its support effect on PtSn/Al2O3 catalyzed propane dehydrogenation - Haowei Wang; Wen-Cui Li; Xinqian Gao; Shuzhen Zhou; Yu Zhang; Fan Wu; An-Hui Lu (Chemical Engineering Journal, 2024)

A multi-parameter control method for maize threshing based on machine learning algorithm optimisation - Chenlong Fan; Dongxing Zhang; Li Yang; Tao Cui; Xiantao He; Mengmeng Qiao; Jialu Sun; Jiaqi Dong (Biosystems Engineering, 2023)

MiR-23a promotes autophagy of yak cumulus cells to alleviate apoptosis via the apoptosis signal-regulating kinase 1/c-Jun N-terminal kinase pathway - Xiaohong Han; Sijiu Yu; Yan Cui; Jingjing Li; Jiangfeng Fan; Libin Wang; Meng Wang; Yangyang Pan; Gengquan Xu (Theriogenology, 2023)

Spatial-temporal characteristics of inorganic anions in the Middle Route of South-North Water Diversion project in Henan province (China) - Tailai Yin; Zhenzhen Cui; Panpan Fan; Pengcheng Lan; Xiaojun Wang; Dongyu Wu; Han Liu; Zhaojin Chen; Yuying Li; Bailian Li (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Exploring the potential of magnetic persimmon tannins-based bio-adsorbent for Cd (II) ions removal from water: Experiment and DFT study - Fan Zhou; Lin Gao; Shunyan Cui; Jing Tian; Tong Wang; Guiyin Li; Zhongmin Wang; Chaoke Qin; Dahong Lin; Weijiang Gan; Zhaojin Ran (Journal of Water Process Engineering, 2023)

Enhancement of catalytic activity of PAl-NaX catalyst for side-chain alkylation of toluene with methanol: Effects of dehydrogenation component Cu - Chengda Li; Yueli Wen; Bin Wang; Maohong Fan; Wenlong Liu; Zheng Cui; Wei Huang (Fuel, 2023)

Bioaccumulation of novel brominated flame retardants in crucian carp (Carassius auratus): Implications for electronic waste recycling area monitoring - Zhaowei Wang; Hongliang Jia; Yan Jiang; Song Cui; Yi-fan Li (Environmental Research, 2023)

Comparative study on the thermal characteristics under different air distribution strategies oriented to non-uniform environment: An indoor experiment - Han Li; Qiuyue Cui; Xiangfei Kong; Man Fan (Building and Environment, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Progress on the roles of zinc in sperm cryopreservation - Yuanyou Li; Shaoyu Qin; Wenfei Cui; Fan Zhao; Meiling He; Zhongliang Jiang (Theriogenology, 2023)

The effect of chronic intermittent hypobaric hypoxia improving liver damage in metabolic syndrome rats through ferritinophagy - Fang Cui; Haichao Mi; Ruotong Wang; Yutao Du; Fan Li; Shiyang Chang; Yangchen Su; Aijing Liu; Min Shi (Pflügers Archiv - European Journal of Physiology, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Preparation of magnetic ZnFe2O4 nanosphere photocatalyst for high concentration ammonia nitrogen wastewater treatment - Fan Gao; Xianyong Guo; Haoxuan Cui; Jing Wang; Jiaxuan Liu; Yinghai Wu; Li Wan; Cuiya Zhang; Guangjing Xu (Journal of Environmental Chemical Engineering, 2023)

Temporal-spatial distributions of road silt loadings and fugitive road dust emissions in Beijing from 2019 to 2020 - Haibin Wang; Lihui Han; Tingting Li; Song Qu; Yuncheng Zhao; Shoubin Fan; Tong Chen; Haoran Cui; Junfang Liu (Journal of Environmental Sciences, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Predicting daily solar radiation using a novel hybrid long short-term memory network across four climate regions of China - Liwen Xing; Ningbo Cui; Li Guo; Daozhi Gong; Shenglin Wen; Yixuan Zhang; Mengying Fan (Computers and Electronics in Agriculture, 2023)

Reforestation substantially changed the soil antibiotic resistome and its relationships with metal resistance genes, mobile genetic elements, and pathogens - Song Zhang; Ting Li; Jinming Hu; Kexin Li; Dong Liu; Haixia Li; Fang Wang; Danhong Chen; Zejin Zhang; Qiuping Fan; Xiaoyong Cui; Rongxiao Che (Journal of Environmental Management, 2023)

Two strategies for rapid and sensitive detection of procalcitonin using carbon dots-encapsulated nanocapsule and magnetic carbon dots as coupled labels - Bo Liu; Siyu Lu; Kun Yang; Xuechen Dou; Xiangling Feng; Haoran Cui; Fan Li; Feng Tian (Chemical Engineering Journal, 2023)

Millettia speciosa Champ cellulose-based hydrogel as a novel delivery system for Lactobacillus paracasei: Its relationship to structure, encapsulation and controlled release - Meng-Fan Li; Hua-Ling Cui; Wen-Yong Lou (Carbohydrate Polymers, 2023)

Linking soil organic carbon dynamics to microbial community and enzyme activities in degraded soil remediation by reductive soil disinfestation - Yanlong Chen; Yuhan Zhang; Cui Li; Risheng Xu; Ziru Pei; Fangchao Li; Yuhong Wu; Fan Chen; Yanru Liang; Zhonghui Li; Xiaohong Tian; Yuheng Wang (Applied Soil Ecology, 2023)

First assessment of optical and microwave remotely sensed vegetation proxies in monitoring aboveground carbon in tropical Asia - Tianxiang Cui; Lei Fan; Philippe Ciais; Rasmus Fensholt; Frédéric Frappart; Stephen Sitch; Jérome Chave; Zhongbing Chang; Xiaojun Li; Mengjia Wang; Xiangzhuo Liu; Mingguo Ma; et al. (Remote Sensing of Environment, 2023)

Effects of calcium supplements on oral bioavailability of fluoride in soil based on In Vivo and In Vitro methods - Yunpeng Li; Naiyi Yin; Xiaolin Cai; Pengfei Wang; Chuanfang Fan; Xuhui Chang; Xiaotong Liu; Ziqi Geng; Liwei Cui; Xin Du; Yanshan Cui (Journal of Hazardous Materials, 2023)

Transport of neonicotinoid insecticides in a wetland ecosystem: Has the cultivation of different crops become the major sources? - Zhikun Liu; Song Cui; Qiang Fu; Fuxiang Zhang; Zulin Zhang; Rupert Hough; Lihui An; Yi-Fan Li; Leiming Zhang (Journal of Environmental Management, 2023)

Fertilizing-induced alterations of microbial functional profiles in soil nitrogen cycling closely associate with crop yield - Ruochen Li; Chengyao Ren; Likun Wu; Xinxin Zhang; Xinyi Mao; Zhen Fan; Weili Cui; Wu Zhang; Gehong Wei; Duntao Shu (Environmental Research, 2023)

Challenges and engineering application of landfill leachate concentrate treatment - Qian Li; Hanlin Cui; Yihao Li; Xin Song; Wenzong Liu; Yongxuan Wang; Haimeng Hou; Hongbo Zhang; You Li; Fan Wang; Jun Song; Hanfeng Ye; et al. (Environmental Research, 2023)

Knockdown of USF2 inhibits pyroptosis of podocytes and attenuates kidney injury in lupus nephritis - Ying Xie; Xiaoying Li; Wenli Deng; Nan Nan; Huimei Zou; Lei Gong; Min Chen; Jie Yu; Peilei Chen; Daolin Cui; Fan Zhang (Journal of Molecular Histology, 2023)

Can the development of renewable energy in China compensate for the damage caused by environmental pollution to residents’ health? - Chenggang Li; Xiangbo Fan; Yuting Wang; Zuogong Wang; Yunxiao Dang; Yuanzheng Cui (Environmental Science and Pollution Research, 2023)

Identifying interactions of linked irrigated lake-groundwater system by combining hydrodynamic and hydrochemical method - MuRong Li; Jianmin Bian; Yu Wang; Xinying Cui; Yuanfang Ding; Xiaoqing Sun; Fan Wang; Yuqi Lou (Environmental Science and Pollution Research, 2023)

A long-ignored unique ecosystem of cavefishes in the southern karst: achievements, challenges, and prospects - Li Wu; Cui Fan; Changting Lan; Jing Yu; Huamei Wen; Qin Yang; Ning Xiao; Jiang Zhou (Environmental Science and Pollution Research, 2023)

N-doped biochar mediated peroxydisulfate activation for selective degradation of bisphenol A: The key role of potential difference-driven electron transfer mechanism - Jiaqu Tan; Xinmin Chen; Mengru Shang; Jiannan Cui; Dongya Li; Fan Yang; Zhen Zhang; Haotian Zhang; Qitang Wu; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2023)

Panicle removal delays plant senescence and enhances vegetative growth improving biomass production in switchgrass - Chunqiao Zhao; Yuesen Yue; Juying Wu; John Scullion; Qiang Guo; Qinghai Wang; Cui Li; Xiuyun Wan; Xincun Hou; Xifeng Fan (Biomass and Bioenergy, 2023)

Associations of Multiple Serum Trace Elements with Abnormal Sleep Duration Patterns in Hospitalized Patient with Cirrhosis - Yangyang Hui; Gaoyue Guo; Lihong Mao; Yifan Li; Mingyu Sun; Xiaoyu Wang; Wanting Yang; Xiaofei Fan; Kui Jiang; Binxin Cui; Chao Sun (Biological Trace Element Research, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Plasma-reconstructed LaMnO3 nanonetwork supported palladium catalyst for methane catalytic combustion - Jinlin Jiang; Cuicui Wang; Shuai Zhao; Fan Xue; Lei Li; Mifen Cui; Xu Qiao; Zhaoyang Fei (Journal of Environmental Chemical Engineering, 2023)

Inchworm-Inspired soft robot with magnetic driving based on PDMS, EGaIn and NdFeB (PEN) combination - Yanfang Guan; Yansheng Liu; Qilong Wang; Hao Geng; Tangyong Cui; Yuang Hu; Qing Luo; Aonan Li; Wujie Li; Yang Lin; Lin Zhang; Guangyu Liu; et al. (Chemical Engineering Journal, 2023)

Production of antifungal iturins from vegetable straw: A combined chemical-bacterial process - Yuan Yuan; Depeng Chu; Jiajun Fan; Zhenzhen Cui; Rui Wang; Han Zhang; Xiangwei You; Yiqiang Li; Xiaoqiang Wang (Bioresource Technology, 2023)

Combined organic-inorganic fertilization builds higher stability of soil and root microbial networks than exclusive mineral or organic fertilization - Luhua Yang; Renhua Sun; Jungai Li; Limei Zhai; Huiling Cui; Bingqian Fan; Hongyuan Wang; Hongbin Liu (Soil Ecology Letters, 2023)

Weak environmental adaptation of rare phylotypes sustaining soil multi-element cycles in response to decades-long fertilization - Weili Cui; Ruochen Li; Zhen Fan; Likun Wu; Xining Zhao; Gehong Wei; Duntao Shu (Science of The Total Environment, 2023)

Insight into mechanochemical destruction of PFOA by BaTiO3: An electron-dominated reduction process - Li Li; Ruoning Guo; Jie Gao; Jie Liu; Zhiwei Zhao; Xin Sheng; JunYu Fan; Fuyi Cui (Journal of Hazardous Materials, 2023)

Phosphorus release characterization of biochar loaded with inherent and exogenous phosphorus and impact on soil Pb immobilization - Binglu Bao; Hongbiao Cui; Huiting Li; Yuchao Fan; Detian Li; Jing Wei; Jing Zhou; Jun Zhou (Journal of Cleaner Production, 2023)

Arsenic and iron bioavailability in Caco-2 cells: The influence of their co-existence and concentration - Xuhui Chang; Xiaolin Cai; Naiyi Yin; Pengfei Wang; Chuanfang Fan; Xiaotong Liu; Yunpeng Li; Shuping Wang; Liwei Cui; Yanshan Cui (Food and Chemical Toxicology, 2023)

Effects of Kuroshio and Mesoscale Eddy on Fishing Ground Gravity of Neon Flying Squid Ommastrephes bartramii in Northwest Pacific Ocean - Jiasheng Li; Xuesen Cui; Fenghua Tang; Wei Fan; Zhen Han; Zuli Wu (Journal of Marine Science and Engineering, 2023)
Understanding the spatial patterns of neon flying squid is important for the monitoring and management of fishery resources. Mesoscale eddies and the Kuroshio Extension play important roles in the variation of the fishing ground of Ommastrephes bartramii. However, the way in which eddies and the Kuroshio influence the distribution of Ommastrephes bartramii requires further understanding. In this study, the spatial variation in the distribution of fishing activity and the change of fishing ground gravity of squid were analyzed using automatic identification system (AIS) data. There is a positive correlation between the fishing ground gravity in latitudinal direction and Kuroshio Extension indicators based on the high-frequency eddy kinetic energy (EKE), which describes the Kuroshio variations. Furthermore, the Kuroshio Extension indicators show a positive relationship with the number of the eddies generated in the fishing ground. The results suggest that the changes in the dynamics of SST anomalies could be influenced by eddy-shedding processes in the upstream KE and then alter the distribution of the fishing ground for Ommastrephes bartramii. The Kuroshio index (mean high-frequency eddy kinetic energy between 32° and 37° N, 142° and 149° E) can be used as a good indicator of Kuroshio extension variations to investigate the squid fishing ground in the Kuroshio–Oyashio transition area.

Effect of combined aging treatment on biochar adsorption and speciation distribution for Cd(II) - Yuxin Ke; Fuxiang Zhang; Zulin Zhang; Rupert Hough; Qiang Fu; Yi-Fan Li; Song Cui (Science of The Total Environment, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

In Vitro Antifungal Activity of Azoles and Other Antifungal Agents Against Pathogenic Yeasts from Vulvovaginal Candidiasis in China - Siyue Kan; Nana Song; Qiuyu Pang; Huan Mei; Hailin Zheng; Dongmei Li; Fan Cui; Guixia Lv; Ruifang An; Ping Li; Zhengai Xiong; Shangrong Fan; et al. (Mycopathologia, 2023)

Spatial characterization of HCHO and reapportionment of its secondary sources considering photochemical loss in Taiyuan, China - Jingya Hua; Yang Cui; Lili Guo; Hongyan Li; Jie Fan; Yanan Li; Yonghong Wang; Kankan Liu; Qiusheng He; Xinming Wang (Science of The Total Environment, 2023)

Soil texture is an easily overlooked factor affecting the temperature sensitivity of N2O emissions - Peiyuan Cui; Zhixuan Chen; Fenliang Fan; Chang Yin; Alin Song; Tingqiang Li; Hongcheng Zhang; Yongchao Liang (Science of The Total Environment, 2023)

Pb induces ferroptosis in choroid plexus epithelial cells via Fe metabolism - Fan Shi; Haohui Yang; Guogui Sun; Jianmei Cui; Zejin Li; Weixuan Wang; Yanshu Zhang (NeuroToxicology, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Experimental and numerical investigation on dynamic behavior of RC orifice targets subjected to underwater explosions - Guangdong Yang; Yong Fan; Gaohui Wang; Xianze Cui; Qi Li; Zhendong Leng (Engineering Structures, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

Soil sample sizes for DNA extraction substantially affect the examination of microbial diversity and co-occurrence patterns but not abundance - Ting Li; Song Zhang; Jinming Hu; Haiyan Hou; Kexin Li; Qiuping Fan; Fang Wang; Linfeng Li; Xiaoyong Cui; Dong Liu; Rongxiao Che (Soil Biology and Biochemistry, 2023)

Barley β-glucan inhibits digestion of soybean oil in vitro and lipid-lowering effects of digested products in cell co-culture model - Jiaying Li; Yurong Zhou; Jiayan Zhang; Ling Cui; Haina Lu; Ying Zhu; Yansheng Zhao; Songtao Fan; Xiang Xiao (Food Research International, 2023)

3D macro/mesoporous highly reproducible amino-functionalized covalent organic framework nanospheres for fat-rich foodstuffs pretreatment in nontargeted analysis - Yan Qi; Jing Zhang; Li Zhang; Xiangyu Zhou; Wei Li; Jialin Cui; Mengdie Fan; Yushen Jin; Junwang Tang; Jianzhong Shen; Bing Shao (Chemical Engineering Journal, 2023)

Tumor microenvironment activated nanoreactors for chemiluminescence imaging-guided simultaneous elimination of breast tumors and tumor-resident intracellular pathogens - Xinxin Li; Ting Wu; Zefan Zhang; Sha Liu; Hongmei Cui; Zhongxiong Fan; Baodui Wang; Jun Hai (Chemical Engineering Journal, 2023)

Ultralight and flexible silver nanoparticle-wrapped “scorpion pectine-like” polyimide hybrid aerogels as sensitive pressor sensors with wide temperature range and consistent conductivity response - Huikang Xu; Weijun Chen; Chengyang Wang; Tingting Jia; Dezhi Wang; Gang Li; Daoxiang Zhao; Baojun Cui; Zhen Fan; Xupeng Fan; Haitao Zhang; Tenghai Gan; et al. (Chemical Engineering Journal, 2023)

Significant impact of VOCs emission from coking and coal/biomass combustion on O3 and SOA formation in taiyuan, China - Yu Wang; Yang Cui; Qiusheng He; Jie Fan; Yanan Li; KanKan Liu; Lili Guo; Xinming Wang (Atmospheric Pollution Research, 2023)

Spatializing the roughness length of heterogeneous urban surfaces to improve the WRF simulation-Part 2: Impacts on the thermodynamic environment - Chong Shen; Yiming Liu; Ao Shen; Yinping Cui; Xiaoyang Chen; Qi Fan; Pakwai Chan; Chunyan Tian; Zizhao Xie; Chunlin Wang; Jing Lan; Xiaohui Li; et al. (Atmospheric Environment, 2023)

Real-world characterization of carbonaceous substances from industrial stationary and process source emissions - Min Cui; Yuanyuan Xu; Fan Zhang; Caiqing Yan; Jun Li; Mei Zheng; Yingjun Chen (Science of The Total Environment, 2023)

Mitigation effects of air-backed RC slabs retrofitted with CFRP subjected to underwater contact explosions - Guangdong Yang; Yong Fan; Gaohui Wang; Xianze Cui; Qi Li; Zhendong Leng; Ke Deng (Ocean Engineering, 2023)

Dual-bionic, fluffy, and flame resistant polyamide-imide ultrafine fibers for high-temperature air filtration - Yuezhen Hua; Yuyao Li; Zekai Ji; Wang Cui; Zheng Wu; Jie Fan; Yong Liu (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Impacts of mowing and N addition on soil organic phosphorus mineralization rates in a semi-natural grassland in Northeast China - Haiying Cui; Mingcai Fan; Yunbo Wang; Xiaochong Zhang; Wanling Xu; Yanan Li; Wenzheng Song; Jian-Ying Ma; Wei Sun (Plant and Soil, 2023)

Biased Genotype Distributions of Candida albicans Strains Associated with 649 Clinical Vulvovaginal Candidiasis in China - Qiuyu Pang; Weida Liu; Fan Cui; Siyue Kan; Xiaofang Li (Mycopathologia, 2022)

Genomic prediction of drought tolerance during seedling stage in maize using low-cost molecular markers - Ao Zhang; Shan Chen; Zhenhai Cui; Yubo Liu; Yuan Guan; Shuang Yang; Jingtao Qu; Juchao Nie; Dongdong Dang; Cong Li; Xiaomei Dong; Jinjuan Fan; et al. (Euphytica, 2022)
Drought tolerance in maize is a complex and polygenic trait, especially in the seedling stage. In plant breeding, complex genetic traits can be improved by genomic selection (GS), which has become a practical and effective breeding tool. In the present study, a natural maize population named Northeast China core population (NCCP) consisting of 379 inbred lines were genotyped with diversity arrays technology (DArT) and genotyping-by-sequencing (GBS) platforms. Target traits of seedling emergence rate (ER), seedling plant height (SPH), and grain yield (GY) were evaluated under two natural drought stress environments in northeast China. Adequate genetic variations were observed for all the target traits, but they were divergent across environments. Similarly, the heritability of the target trait also varied across years and environments, the heritabilities in 2019 (0.88, 0.82, 0.85 for ER, SPH, GY) were higher than those in 2020 (0.65, 0.53, 0.33) and cross-2-years (0.32, 0.26, 0.33). In total, three marker datasets, 11,865 SilicoDArT markers obtained from the DArT-seq platform, 7837 SNPs obtained from the DArT-seq platform, and 91,003 SNPs obtained from the GBS platform, were used for GS analysis after quality control. The results of phylogenetic trees showed that broad genetic diversity existed in the NCCP population. Genomic prediction results showed that the average prediction accuracies estimated using the DArT SNP dataset under the two-fold cross-validation scheme were 0.27, 0.19, and 0.33, for ER, SPH, and GY, respectively. The result of SilicoDArT is close to the SNPs from DArT-seq, those were 0.26, 0.22, and 0.33. For the trait with lower heritability, the prediction accuracy can be improved using the dataset filtered by linkage disequilibrium. For the same trait, the prediction accuracies estimated with two DArT marker datasets were consistently higher than that estimated with the GBS SNP dataset under the same genotyping cost. The prediction accuracy was improved by controlling population structure and marker quality, even though the marker density was reduced. The prediction accuracies were improved by more than 30% using the significant-associated SNPs. Due to the complexity of drought tolerance under the natural stress environments, multiple years of data need to be accumulated to improve prediction accuracy by reducing genotype-by-environment interaction. Modeling genotype-by-environment interaction into genomic prediction needs to be further developed for improving drought tolerance in maize. The results obtained from the present study provides valuable pathway for improving drought tolerance in maize using GS.

A review of spatiotemporal patterns of neonicotinoid insecticides in water, sediment, and soil across China - Zhikun Liu; Leiming Zhang; Zulin Zhang; Lihui An; Rupert Hough; Peng Hu; Yi-Fan Li; Fuxiang Zhang; Shuang Wang; Yunqing Zhao; Yuxin Ke; Song Cui (Environmental Science and Pollution Research, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Recent Progress in Modeling and Control of Bio-Inspired Fish Robots - Boai Sun; Weikun Li; Zhangyuan Wang; Yunpeng Zhu; Qu He; Xinyan Guan; Guangmin Dai; Dehan Yuan; Ang Li; Weicheng Cui; Dixia Fan (Journal of Marine Science and Engineering, 2022)
Compared with traditional underwater vehicles, bio-inspired fish robots have the advantages of high efficiency, high maneuverability, low noise, and minor fluid disturbance. Therefore, they have gained an increasing research interest, which has led to a great deal of remarkable progress theoretically and practically in recent years. In this review, we first highlight our enhanced scientific understanding of bio-inspired propulsion and sensing underwater and then present the research progress and performance characteristics of different bio-inspired robot fish, classified by the propulsion method. Like the natural fish species they imitate, different types of bionic fish have different morphological structures and distinctive hydrodynamic properties. In addition, we select two pioneering directions about soft robotic control and multi-phase robotics. The hybrid dynamic control of soft robotic systems combines the accuracy of model-based control and the efficiency of model-free control, and is considered the proper way to optimize the classical control model with the intersection of multiple machine learning algorithms. Multi-phase robots provide a broader scope of application compared to ordinary bionic robot fish, with the ability of operating in air or on land outside the fluid. By introducing recent progress in related fields, we summarize the advantages and challenges of soft robotic control and multi-phase robotics, guiding the further development of bionic aquatic robots.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Migration and Deposition Characteristics of Particles in Sand Layers with Fluctuating Water Levels - Xianze Cui; Tao Wen; Jin Li; Dazhou Wu; Yong Fan; Ying Jin; Siyuan He; Yucong Pan (Water, Air, & Soil Pollution, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Magnetoresponsive nanozyme: magnetic stimulation on the nanozyme activity of iron oxide nanoparticles - Yuan He; Xiaoyong Chen; Ye Zhang; Yanyun Wang; Mengyao Cui; Galong Li; Xiaoli Liu; Haiming Fan (Science China Life Sciences, 2022)

Dexmedetomidine Alleviates Lipopolysaccharide-Induced Hippocampal Neuronal Apoptosis via Inhibiting the p38 MAPK/c-Myc/CLIC4 Signaling Pathway in Rats - Yongping Chen; Lin Li; Jiuyan Zhang; Hailin Cui; Jiucheng Wang; Chuqiao Wang; Mingxian Shi; Honggang Fan (Molecular Neurobiology, 2021)

Two Foxo1 homologues in the orange-spotted grouper Epinephelus coioides: sequences, expression, and possible involvement in the activation of cyp19a1a expression in the ovary - Yunfeng Ning; Miao Fan; Qiongyou Liu; Huijie Lu; Shangyong Qian; Xin Cui; Feiyan Meng; Xi Li; Xing Xu; Shu Sun; Youwei Zhang; Lihong Zhang; et al. (Fish Physiology and Biochemistry, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

The interaction of MYB, bHLH and WD40 transcription factors in red pear (Pyrus pyrifolia) peel - Daolei Cui; Shuxin Zhao; Huini Xu; Andrew C. Allan; Xiaodong Zhang; Lei Fan; Limei Chen; Jun Su; Quan Shu; Kunzhi Li (Plant Molecular Biology, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

The effects of plant resource inputs on the energy flux of soil nematodes are affected by climate and plant resource type - Lina Zhao; Binbin Yu; Mengmeng Wang; Jie Zhang; Zhifeng Shen; Yang Cui; Junyong Li; Ji Ye; Weizhong Zu; Xiaojing Liu; Zongji Fan; Shenglei Fu; et al. (Soil Ecology Letters, 2021)

Nucleoprotein phosphorylation site (Y385) mutation confers temperature sensitivity to influenza A virus due to impaired nucleoprotein oligomerization at a lower temperature - Weinan Zheng; Liang Cui; Minghui Li; Yun Li; Wenhui Fan; Limin Yang; Jing Li; Lei Sun; Wenjun Liu (Science China Life Sciences, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

Transcriptomic Analysis of Pacific Oyster (Crassostrea gigas) Zygotes Under Hypotonic Triploid Induction - Yangchun Li; Zhaoping Wang; Yuting Cui; Peizhen Ma; Xuekai Zhang; Chao Fan (Journal of Ocean University of China, 2021)

Dietary exposure of general Chinese population to fatty acid esters of 3-monochloropropane-1, 2-diol (3-MCPD) from edible oils and oil-containing foods - Xia Cui; Lei Zhang; Pingping Zhou; Zhaoping Liu; Sai Fan; Dajin Yang; Jianwen Li; Qing Liu (Food Additives & Contaminants: Part A, 2021)

Magnesium promotes root growth and increases aluminum tolerance via modulation of nitric oxide production in Arabidopsis - Dongxu Li; Wenna Ma; Jian Wei; Yawen Mao; Zhongping Peng; Jiarong Zhang; Xiangying Kong; Qinqin Han; Wei Fan; Ye Yang; Jianghua Chen; Liangquan Wu; et al. (Plant and Soil, 2020)

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Cortical morphometry alterations in brain regions involved in emotional, motor-control and self-referential processing in patients with functional constipation - Chunxin Hu; Li Liu; Lei Liu; Junwang Zhang; Yang Hu; Wenchao Zhang; Yueyan Ding; Yuanyuan Wang; Zhida Zhang; Karen M. von Deneen; Long Qian; Huaning Wang; et al. (Brain Imaging and Behavior, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

GPR based RTM imaging technology for estimating rhizome diameters and application in the western China mining area - Fan Cui; Shuai Li; Jiong-Xuan Yuan; Jie-Bin Bai; Yu-Xuan Zhao; Ying-Ging Zhou (Applied Geophysics, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Expressional and Functional Verification of the Involvement of CmEXPA4 in Chrysanthemum Root Development - Hong Ren; Li-zhu Wen; Yun-hui Guo; Yuan-yuan Yu; Cui-hui Sun; Hong-mei Fan; Fang-fang Ma; Cheng-shu Zheng (Journal of Plant Growth Regulation, 2019)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Nicotine in action: cigarette smoking modulated homotopic functional connectivity in schizophrenia - Wei Liao; Siqi Yang; Jiao Li; Yun-Shuang Fan; Xujun Duan; Qian Cui; Huafu Chen (Brain Imaging and Behavior, 2019)

Modeling primary and secondary fractionation effects and atmospheric transport of polychlorinated biphenyls through single-source emissions - Song Cui; Qiang Fu; Chongguo Tian; Zulin Zhang; Rupert Hough; Zhenxing Shen; Jianmin Ma; Lihui An; Yi-Fan Li (Environmental Geochemistry and Health, 2019)

Tamarixetin protects against cardiac hypertrophy via inhibiting NFAT and AKT pathway - Cheng Fan; Yuan Li; Hui Yang; Yuqian Cui; Hao Wang; Heng Zhou; Jianning Zhang; Binfeng Du; Qian Zhai; Dawei Wu; Xiaomei Chen; Haipeng Guo (Journal of Molecular Histology, 2019)

Complete genomic sequence and organization of a novel mycovirus from Phoma matteuccicola strain LG915 - Fan Zheng; Gang Xu; Jia Zhou; Changping Xie; Hongguang Cui; Weiguo Miao; Zhensheng Kang; Li Zheng (Archives of Virology, 2019)

CNOT3 contributes to cisplatin resistance in lung cancer through inhibiting RIPK3 expression - Lin Jing; Meng-En Zhai; Jian Cui; Xin-Yu Fan; Yuan-Yuan Cheng; Jian-Li Jiang; Zhi-Nan Chen (Apoptosis, 2019)

Increasing livestock wastewater application in alternate-furrow irrigation reduces nitrification gene abundance but not nitrification rate in rhizosphere - Yuan Liu; Andrew L. Neal; Xiaoxian Zhang; Erping Cui; Feng Gao; Xiangyang Fan; Chao Hu; Zhongyang Li (Biology and Fertility of Soils, 2019)

A multi-risk assessment framework for agricultural land use optimization - Haojie Cui; Ping Guo; Mo Li; Shanshan Guo; Fan Zhang (Stochastic Environmental Research and Risk Assessment, 2019)

Prediction of curtain grouting efficiency based on ANFIS - Xiaochao Li; Denghua Zhong; Bingyu Ren; Guichao Fan; Bo Cui (Bulletin of Engineering Geology and the Environment, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

Subdivision and age of the Yanchang Formation and the Middle/Upper Triassic boundary in Ordos Basin, North China - Shenghui Deng; Yuanzheng Lu; Zhong Luo; Ru Fan; Xin Li; Yi Zhao; Xueying Ma; Rukai Zhu; Jingwei Cui (Science China Earth Sciences, 2018)

Engineering herbicide-resistant watermelon variety through CRISPR/Cas9-mediated base-editing - Shouwei Tian; Linjian Jiang; Xiaxia Cui; Jie Zhang; Shaogui Guo; Maoying Li; Haiying Zhang; Yi Ren; Guoyi Gong; Mei Zong; Fan Liu; Qijun Chen; et al. (Plant Cell Reports, 2018)

Comparison of clogging induced by organic and inorganic suspended particles in a porous medium: implications for choosing physical clogging indicators - Yang Wang; Mingxin Huo; Qi Li; Wei Fan; Jiakuan Yang; Xiaochun Cui (Journal of Soils and Sediments, 2018)

Levels, spatial variations, and possible sources of polycyclic aromatic hydrocarbons in sediment from Songhua River, China - Song Cui; Kunyang Li; Qiang Fu; Yi-Fan Li; Dong Liu; Shang Gao; Zihan Song (Arabian Journal of Geosciences, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Soybean and cottonseed meals are good candidates for fishmeal replacement in the diet of juvenile Macrobrachium nipponense - Yu-Juan Huang; Nan-Nan Zhang; Wu-Jiang Fan; Yan-Yan Cui; Samwel Mchele Limbu; Fang Qiao; Yun-Long Zhao; Li-Qiao Chen; Zhen-Yu Du; Dong-Liang Li (Aquaculture International, 2018)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Bisphenol A Represses Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells through Downregulating the Expression of Insulin-like Growth Factor 1 - Boxian Huang; Song Ning; Qinjing Zhang; Aiqin Chen; Chunyan Jiang; Yugui Cui; Jian Hu; Hong Li; Guoping Fan; Lianju Qin; Jiayin Liu (Molecular Neurobiology, 2017)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing - Jin-jun Zhang; Meng-meng Cui; Da Fan; De-shan Zhang; Hui-xin Lian; Zhao-yin Yin; Jin Li (Environmental Science and Pollution Research, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

DISC1 Ser704Cys impacts thalamic-prefrontal connectivity - Bing Liu; Lingzhong Fan; Yue Cui; Xiaolong Zhang; Bing Hou; Yonghui Li; Wen Qin; Dawei Wang; Chunshui Yu; Tianzi Jiang (Brain Structure and Function, 2015)

Using enriched stable isotope technique to study Cu bioaccumulation and bioavailability in Corbicula fluminea from Taihu Lake, China - Wenhong Fan; Jinqian Ren; Chenguang Wu; Cheng Tan; Xiaolong Wang; Minming Cui; Kuang Wu; Xiaomin Li (Environmental Science and Pollution Research, 2014)

Molecular phylogeny of Cotoneaster (Rosaceae) inferred from nuclear ITS and multiple chloroplast sequences - Feifei Li; Qiang Fan; Qingyan Li; Sufang Chen; Wei Guo; Dafang Cui; Wenbo Liao (Plant Systematics and Evolution, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Identification of MHC class I sequences in four species of Macaca of China - Xiang Yan; Aixue Li; Lin Zeng; Yuhua Cao; Jianbin He; Longbao Lv; Lihua Sui; Huahu Ye; Junwen Fan; Xiaoxia Cui; Zhaozeng Sun (Immunogenetics, 2013)

Forward simulation of root’s ground penetrating radar signal: simulator development and validation - Li Guo; Henry Lin; Bihang Fan; Xihong Cui; Jin Chen (Plant and Soil, 2013)

Impact of root water content on root biomass estimation using ground penetrating radar: evidence from forward simulations and field controlled experiments - Li Guo; Henry Lin; Bihang Fan; Xihong Cui; Jin Chen (Plant and Soil, 2013)

MCM7 Expression Is Altered in Rat After Spinal Cord Injury - Jiajia Chen; Zhiming Cui; Weidong Li; Aiguo Shen; Guanhua Xu; Guofeng Bao; Yuyu Sun; Lingling Wang; Jianbo Fan; Jinlong Zhang; Longfei Yang; Zhiming Cui (Journal of Molecular Neuroscience, 2013)

Up-regulation of Smurf1 after spinal cord injury in adult rats - Debao Li; Jinlong Zhang; Wei Huang; Huricha Jin; Aiguo Shen; Longfei Yang; Jian Liu; Jianbo Fan; Qingzhong Zhou; Hai Wen; Yong Hu; Zhiming Cui (Journal of Molecular Histology, 2013)

Expression of RBMX After Spinal Cord Injury in Rats - Jinlong Zhang; Debao Li; Aiguo Shen; Hui Mao; Huricha Jin; Wei Huang; Dawei Xu; Jianbo Fan; Jiajia Chen; Longfei Yang; Zhiming Cui (Journal of Molecular Neuroscience, 2013)

Application of ground penetrating radar for coarse root detection and quantification: a review - Li Guo; Jin Chen; Xihong Cui; Bihang Fan; Henry Lin (Plant and Soil, 2013)

Syntheses and antiproliferative activity of some sulfated hydroximinosterols - Yanmin Huang; Jianguo Cui; Ying Li; Lei Fan; Yanxiao Jiao; Shaoyang Su (Medicinal Chemistry Research, 2013)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Urban transformation of a metropolis and its environmental impacts - Zhan Tian; Guiying Cao; Jun Shi; Ian McCallum; Linli Cui; Dongli Fan; Xinhu Li (Environmental Science and Pollution Research, 2012)

The analysis of water vapor distribution over Taklimakan Desert - XiaoYang Liu; JieTai Mao; Fan Zhang; CaiXia Cui; Dian Liu; Jun Li; Ling Zhao (Science China Earth Sciences, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Neural Network Analysis of Ex-vivo Expansion of Hematopoietic Stem Cells - Xiubo Fan; Tianqing Liu; Xiangqin Li; Yang Liu; Xuehu Ma; Zhanfeng Cui (Annals of Biomedical Engineering, 2007)

Expression of cysteine sulfinate decarboxylase (CSD) in male reproductive organs of mice - Jian Hua Li; Ya Qin Ling; Jing Jing Fan; Xiao Ping Zhang; Sheng Cui (Histochemistry and Cell Biology, 2006)